Metagenomic insights into suppressing antibiotic-resistant bacteria in mesocosm-scale constructed wetlands: calamus-biochar alleviates selective pressure and disrupts genetic co-occurrence network - Wei Wu; Yu Wang; Tian-Bao Yang; Xian-Kai Zhang; Bing-Dang Wu; Jin-Long Zhuang; Qian-Yi Cao; Shuo Song; Wei Li; Tian-Yin Huang; Xiao-Yi Xu (Bioresource Technology, 2027)

The mercury-nitrogen nexus: Trade-off between nitrous oxide emissions and mercury methylation in rice paddy systems - Rong Huang; Yuzhu Huang; Qinghua Zhou; Jiayue Zhou; Xingyu Li; Ouping Deng; Bing Li; Bo Meng; Jiang Liu; Xinbin Feng (Water Research, 2026)

Synergistic roles of fine-sediment deposition and phosphorus fraction dynamics in internal phosphorus stability during large reservoir operation - Jie Zhang; Yuhan Wang; Jiacong Huang; Yanhong Wu; Liyuan Yang; Zhilin Zhong; Xia Li; Roland Bol; Haijian Bing (Water Research, 2026)

Antifungal effects of carvacrol on Penicillium verrucosum growth in refrigerated wet noodles - Hao Li; Ying-Ying Wang; Yang-Yong Lv; Huan-Chen Zhai; Yuan-Sen Hu; Fu-Zhuan Wang; Liang Huang; Shuai-Bing Zhang (International Journal of Food Microbiology, 2026)

Rock breaking characteristics of high-temperature granite under swirling jets impingement: Implication for hot dry rock extraction using radial jet drilling - Huan Li; Wenbin Li; Chenrui Guo; Bing Xi; Jingbin Li; Zhongwei Huang; Gensheng Li (International Journal of Rock Mechanics and Mining Sciences, 2026)

Impact behavior of seawater sea-sand concrete beams enhanced with high corrosion resistant bars under marine environments: Experimental study and lifetime prediction - Kai Qian; Shi-hao Wu; Bing Liu; Ting Huang; Yang Ming; Zhi Li (Engineering Structures, 2026)

A Neoproterozoic arc-backarc system in the northern Yangtze Block: Implications for crustal growth and Rodinia reconstructions - Chao Chen; Hao Deng; Jin-Ling Yuan; Timothy Kusky; Qiang Chen; Zhen-Bing She; Ling-Yao Kong; Jiang Zhu; Hong-Mei Li; Jing-Meng Huang; Guo-Hu Wang; Cheng Yang; et al. (Earth-Science Reviews, 2026)

Biomass-derived Fe3C@CNT catalyst for catalytic ozonation through confinement-enhanced electron transfer and ozone activation - Tian He; Shaosong Huang; Ping Chen; Guangzheng Zhuang; Bing Tang; Ping Li; Liying Bin; Yunqiang Yi; Weirui Chen; Laisheng Li (Chemical Engineering Journal, 2026)

Photoreactivity of dissolved organic matter drives abiotic vivianite formation at sediment–water interfaces - Shang Yang; Andong Hu; Ruiyuan Wang; Wei Yu; Xiaofeng Wu; Yuefei Huang; Shungui Zhou; Bing Li; Guangqian Wang (Water Research, 2026)

Machine learning-integrated multi-objective application and optimization framework for sulfur-based reactive filler towards nutrient removal - Jia-Min Xu; Jia-Qiang Lv; Wen-Ke He; Hong-Cheng Wang; Xiang-Li Zeng; Yu-Qi Wang; Wan-Xin Yin; Fang Huang; Gui-Jiao Zhang; Heng Dong; Yanchen Liu; Aijie Wang; et al. (Water Research, 2026)

The Scaling Law in remote sensing mapping for model performance forecasting and reference sample optimization - Yuanhong Liao; Yuqi Bai; Shuang Chen; Jie Wang; Yanping You; Zhou Chen; Haoru Wu; Huabing Huang; Wenrui Li; Mingrun Zang; Zimeng Wang; Xinan Zhang; et al. (Remote Sensing of Environment, 2026)

SlROP4 negatively regulates drought tolerance in tomato - Chao Cheng; Min Li; Bing Sun; Wenhui Huang; Shanwei Li; Qiangnan Feng; Feng Xiong; Sha Li (Plant Science, 2026)

Single-site amino acid residue mutation reshapes the characteristics of double bond positions for protostadienol-type triterpenols - Pengyang Lin; Yunpeng Wang; Bing Li; Xuebingting Zhang; Baolian Fan; Ruoshi Huang; Zhongju Ji; Fan Zhang; Jingcai Liang; Lixin Duan (Phytochemistry, 2026)

Spatiotemporal stratified flow analysis: A framework detecting associations between urban facilities and stratified human mobility patterns - Jianyu Li; Mingxing Hu; Shumin Wang; Ziye Liu; Jingyue Huang; Yueying Li; Fan Shi; Bing Han; Hui Wang (Journal of Transport Geography, 2026)

Multi-scale mechanistic elucidation of hydrogen generation in chemical looping gasification of lignite using carbide slag - Xujie Luo; Senlin Dong; Jie Yang; Binbin He; Dongyang Li; Liping Ma; Bing Huang; Liang Chen; Qihong Cen; Heping Zeng; Rui Nie; Lan Shao (Journal of Environmental Chemical Engineering, 2026)

Measuring the spatial explicitness of GeoAI and geospatial foundation models: A systematic review and future roadmap - Bing Zhou; Xiao Huang; Siqin Wang; Gengchen Mai; Diya Li; Zhangyu Wang; Qiusheng Wu; Huan Ning; Junbo Wang; Qifan Wu; Yuhao Jia; Ruomei Wang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Deep learning for automated rock core image analysis: Weathering classification, fracture detection, and 3D geological modelling - Zhihang Li; Mengqi Huang; Huamei Zhu; Yaolan Tang; Jian Zhao; Qian-Bing Zhang (International Journal of Rock Mechanics and Mining Sciences, 2026)

Corrigendum to “Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system” [Estuar. Coast Shelf Sci. 340 (2026) 110113] - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Transition of energy release mode in confined internal explosions: The dominant role of structural confinement over material properties - Ying Zhou; Tao Wang; Xiao-bing Bian; Xu-dong Zhang; Ya-li Guo; Guang-yan Huang (Engineering Structures, 2026)

Perylene-derived ferroptotic exhaustion and tumor angiogenesis remodeling to potentiate antitumor immunity - Jingjing Huang; Haoyu Qi; Bing Shi; Xinting Huang; Xuejie Zhao; Chunli Li; Yongwei Huang (Chemical Engineering Journal, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Quantum chemistry unifies phosphorus removal and recovery through environmental affinity - Degui Gao; Xiaofeng Wu; Yuefei Huang; Bing Li (Water Research, 2026)

Deciphering the effects of sulfonamide antibiotics on denitrification from a metagenomic perspective: inhibition of nitrite reduction and succession patterns of functional microorganisms - Qinmao Zhou; Yuyang Wang; Hebin Liang; Jin Huang; Jiayu Zhang; Ke Yu; Lin Lin; Xiaoyan Li; Bing Li (Journal of Hazardous Materials, 2026)

Depositional characteristics of the great flood along the Juma River, North China Plain, in 2023 - Wei Lv; Tianyu Du; Qinghai Xu; Yuecong Li; Huafang Huang; Shuang Gao; Nan Yang; Yuejie Wu; Bing Li (Geomorphology, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Mechanistic insights into the comparative ecotoxicity of PFOS and its emerging alternatives in zebrafish: An integrated multi-biomarker and molecular modeling approach - Jingwen Zhang; Yunchen Huang; Jun Wang; Jinhua Wang; Zhongkun Du; Bing Li; Yue Yang; Lusheng Zhu (Environmental Research, 2026)

Hierarchical hemispheres microstructure-based iontronic pressure sensor with high sensitivity and wide linear range for gait analysis - Xiaohui Guo; Hao Guo; Bing Hu; Yunjie Peng; Chuanwen Li; Shuting Cao; Junhao Li; Honglin Chen; Zhiyuan Liu; Ming Hou; Ting-Jung Lin; Yunong Zhao; et al. (Chemical Engineering Journal, 2026)

Humic acid-mediated biomineralization of high-purity struvite from copper-containing wastewater for phosphorus recovery - Ye Wang; Hanbing Li; Bing Li; Xiaoxiong Wang; Wei Yu; Shungui Zhou; Yuefei Huang (Chemical Engineering Journal, 2026)

Pd single atoms anchored on mesoporous C3N5: An exceptional photocatalyst for hydrogen production - Yang Wang; Cun-Feng Fan; Jiao-Yan Li; Xiao-Qin Zheng; Xuan-Yi Liu; Ying Zhou; Jiahui Kou; Hengming Huang; Lin-Bing Sun (Chemical Engineering Journal, 2026)

Molecular disruption of neuroinflammatory and metabolic pathways mediates triclosan-induced depressive-like behavior in zebrafish - Danting Wang; Junping Liu; Ruixue Zhou; Bing Han; Chunxia Chen; Wentong Meng; Li Qin; Limei Sun; Bin Tan; Chunyan Huang (Toxicology and Applied Pharmacology, 2026)

Retraction notice to “Determining the spatial non-stationarity underlying social and natural environment in thyroid cancer in China” [Sci. Total Environ. 870 (2023) 162009] - Xiyu Zhang; Yongqiang Lai; Xiaodan Bai; Bing Wu; Wenjing Xiang; Chenxi Zhang; Guihong Geng; Wenqing Miao; Qi Xia; Qunhong Wu; Huiying Yang; Yanjie Wang; et al. (Science of The Total Environment, 2026)

A dual-polarimetric SAR oil spill detection model with background noise suppression and adaptive polarimetric feature weighting - Yikai Huang; Bingxin Liu; Lei Bing; Baozhan Liu; Lingxiao Cheng; Ying Li (Regional Studies in Marine Science, 2026)

Quantitative attribution of seasonal runoff variations in the Yellow River Basin under unsteady conditions using a modified Budyko framework - Junjie Wang; Yuning Chi; Shaoxiong Zhang; Bing Shi; Liting Zhang; Chenjun Du; Xin Li; Baoqi Li; Liqin Yang; Lei Huang; Dian Yuan; Kaiyang Qiu; et al. (Journal of Hydrology, 2026)

TLR4 knockout ameliorates acute LPS-sensitized tolvaptan-induced idiosyncratic liver injury by disrupting drug metabolism, inflammation, and bile acid homeostasis - Xin Jiang; Yi-xin Hu; Bing-yu Cheng; Jing-wen Hu; Yu-qing Zhao; San-lan Wu; Heng Li; Li-Meng Gong; Guang Feng; Dan Li; Lu-qin Si; Jian-geng Huang (Food and Chemical Toxicology, 2026)

A flexible piezoresistive pressure sensor with an interlocking microstructure based on modulated corona electric field - Chenghang Yu; Jian Xu; Fu Lv; Bing Liu; Juan Li; Xin Li; Zijian Hong; Yongjun Wu; Yuhui Huang (Chemical Engineering Journal, 2026)

Source-specific oxidative potential and health risks of PM2.5-bound toxic elements in Xiamen Port: Insights into ship emission contributions - Si-Min Zhao; Qi-Yu Miao; Jia-Min Li; Xin-Ye Wu; Bing-Qi Jiang; Li-Xiong He; Yi-Jing Liu; Zhi Huang; Chung-Shin Yuan; Shui-Ping Wu (Atmospheric Pollution Research, 2026)

Combined shading and waterlogging stress threaten grain mineral nutrition of wheat - Junhao Xu; Zenghui Guo; Jiangyi Shi; Jiwei Huang; Haoran Li; Liujun Xiao; Leilei Liu; Liang Tang; Weixing Cao; Yan Zhu; Bing Liu (Plant and Soil, 2026)

Comparative effects of digestion residue-derived and corn straw biochar on free-living diazotrophs in nitrogen-deficient calcareous purple soil - Junwen Zhao; Yuting Chen; Haiyan Zhang; Yulan Chen; Bing Li; Muhammad Bilal Khan; Yingjie Wu; Xiaoyan Tang; Huanxiu Li; Rong Huang; Qiang Xu; Qiquan Li; et al. (Biology and Fertility of Soils, 2026)

Chemical constituents from the roots of Illigera celebica - Si-Feng Yang; Lin-Wen Yi; Qiu-Xia Huang; Xing-Meng Luo; Xiao-Bing Su; Lin Hu; Wen-Ting Li; Xiang-Zhong Huang; Meng-Yuan Jiang (Natural Product Research, 2026)

Lipopolysaccharide promotes rheumatoid arthritis by enhancing Wnt7b mediated macrophage-FLS communication - Bing Wang; Yingqiu Song; Wenbo Xu; Jiaqing Chen; Yurong Huang; Xinyue Zhou; Yikang Cai; Aixin Xia; Yanping Li; Liwei Jiang; Faxue Liao; Jian Huang; et al. (Inflammation Research, 2026)

Molecular characterization of Echinococcus granulosus EGR-02244 and its functional role in canine peripheral blood mononuclear cells - Juncheng Huang; Yanyan Zhang; Xinwen Bo; Xinwei Feng; Jing Li; Xuke Cheng; Jiaxin Zhao; Jianan Zhao; Bing Li; Linying Wei; Yan Sun; Meng Qi; et al. (Veterinary Parasitology, 2026)

Microbial lifestyles driven by C: N stoichiometric imbalance govern responses of carbon metabolism to nitrogen addition - Bo Kang; Rong Huang; Xun Yan; Linkang Chen; Shanghong Chen; Youlin Luo; Xiaoyan Tang; Yingjie Wu; Qi Tao; Qiang Xu; Changquan Wang; Bing Li (Soil Biology and Biochemistry, 2026)

Undescribed triterpenoid ellagitannins from Castanopsis calathiformis and their potential antiproliferative and hypoglycemic activity - Ya-feng Wang; Ying-rong Bao; Rui-jie He; Nao Pang; Zhang-bin Liu; Bing-yuan Yang; Gui-qin Li; Yong-lin Huang (Phytochemistry, 2026)

Apigenin mitigates cigarette smoke-elicited lung impairment via the orchestration of the PPARγ/PGC1α-FATP2 pathway and the amelioration of the gut microenvironment - Longfei Lv; Sijie Zhang; Bing Huang; Li Ren; Jie Zhang; Zheng Ma (Food Bioscience, 2026)

The mediation and interaction roles of hypertension on the pathway between occupational noise and cardiac arrhythmia: insights from a large cross-sectional occupational population of 229,686 workers - Zhiqiang Li; Wenjing Wu; Xinyue Li; Bing Xia; Shao Lin; Xiaowen Wang; Xudan Chen; Yanji Qu; Ziqiang Lin; Jinghua Li; Guanghui Dong; Yongshun Huang; et al. (Environmental Pollution, 2026)

Unraveling the critical role of PrOx spatial distribution on cu in steering CO2 reduction toward multicarbon products - Xiangbei Wan; Shengxi Zhao; Bing Huang; Hao Zeng; Canyan Yang; Pengwu Jiang; Yu Liu; Lei Chen; Zhenglong Li (Chemical Engineering Journal, 2026)

Synthesis of BMP wrist epitope-derived peptide functionalized bioink for 3D bioprinting of tissue-engineered bone constructs - Fei Huang; Guozhen Wei; Ying Zhang; Bing Wu; Yaoqing Chen; Yaoyu Qiu; Jingfeng Li; Gui Wu (Chemical Engineering Journal, 2026)

Experimental Investigation into the Effect of Process Parameters on Borehole Formation in Bedded Shale by Swirling Abrasive Water Jet - Kang Cheng; Zhongwei Huang; Jingru Hu; Jingbin Li; Bing Xi; Tianshu Wang; Huan Li; Gensheng Li (Rock Mechanics and Rock Engineering, 2026)

Layered manure facilitates phosphorus mobilization mediated by putative keystone taxa among phoD-harboring bacteria - Linkang Chen; Rong Huang; Xiaoyan Tang; Bo Kang; Yijian Zheng; Zongjin Zhang; Changquan Wang; Bing Li (Applied Soil Ecology, 2026)

In vitro nephroprotective indolizidine alkaloids from marine-derived Streptomyces sp. KIB629 - Xiaowei Guo; Lei Wang; Xin He; Bing-Yi Xu; Jun-Jie Zhang; Jian-Ping Huang; Wei Li; Sheng-Xiong Huang; Jing Yang; Ya-Tuan Ma (Natural Product Research, 2026)

DeepLab-AFOS: A marine oil spill detection method based on advantageous features from polarimetric SAR - Yikai Huang; Bingxin Liu; Baozhan Liu; Ying Li; Lei Bing; Lingxiao Cheng (Marine Pollution Bulletin, 2026)

Ectoine modulates mixotrophic denitrification pathway partitioning to sustain stable nitrogen and phenol removal under hypersaline stress - Jingwen Song; Ya-Nan Hou; Ran Li; Zengyue Feng; Ai-Jie Wang; Nanqi Ren; Wei Wei; Bing-Jie Ni; Cong Huang (Water Research, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Corrigendum to “Enhanced ligand-ligand donor-acceptor interactions via DBD plasma for MOFs with bimetallic Fe-Co active sites for H2O2 detection” [J. Environ. Chem. Eng. 14 (2026) 122000] - Min Li; Juanjuan Geng; Bing Feng; Tianyu Luan; Xumei Tao; Liang Huang (Journal of Environmental Chemical Engineering, 2026)

Coaxial electrospun TiO2@CuO heterojunctions with interfacial charge rearrangement for photothermal oxidation of toluene - Weimin Huang; Ke-Xin Li; Shuzhuo Bai; Shanshan Chen; Fanbin Meng; Bing Qin; Yuning Yang; Zonghui Liu; Wen-Tao Zheng; Zhun Hu (Journal of Environmental Chemical Engineering, 2026)

Season-dependent effects of legume inclusion and phosphorus fertilization on soil phosphorus cycling and crop productivity - Zhen Chen; Xin Wang; Shou-Bing Huang; Simone Graeff-Hönninger; Sebastian Munz; Peter Hahn; Si Shen; Shun-Li Zhou (European Journal of Agronomy, 2026)

Multifunctional interface engineering enables high efficiency of semi-transparent CsPbBr3 solar cells - Ankang Shu; Mingming Li; Jiawei Song; Zhengyang Li; Qian Wang; Shangwei Huang; Jiahao Cheng; Wenjian Shen; Cong Geng; Rui Chen; Guijie Liang; Jun Yao; et al. (Chemical Engineering Journal, 2026)

Antibiotic resistance genes in drinking water: Absolute abundance, mobility, and hosts across the source-to-tap continuum - Jie Liu; Renxin Zhao; Jin Huang; Uli Klümper; Ke Yu; Jiayu Zhang; Guijuan Zhang; Thomas U. Berendonk; Ryo Honda; Yang Yu; Jian Sun; George Wells; et al. (Chemical Engineering Journal, 2026)

Elevated CO2 accelerates mineral-protected organic carbon loss in the upland rhizosphere after paddy drainage - Xun Yan; Zhifan Li; Bo Kang; Tao Li; Linkang Chen; Junwen Zhao; Bing Li; Youlin Luo; Yingjie Wu; Rong Huang; Xiaoyan Tang; Qiang Xu; et al. (CATENA, 2026)

Combining puncture testing with discrete element simulation to predict the mechanical response of Rosa roxburghii - Feng Qian; Zhiping Xie; Nan Huang; Xing Li; Yuexin Zhong; Bing Sun; Shetan Hu; Sipeng Wang; Jinping Wu (Journal of Stored Products Research, 2026)

RDX as the sole nitrogen source affects the nitrogen metabolism in Rhodococcus sp. LMD - Songwei Hu; Mengdi Li; Yaya Huang; Yanchao Li; Songrui Zhang; Wenjia Li; Bing Lin; Jiaxin Zhengchen; Qi Lv; Xuanrui Shen; Huibin Zou; Fengbing Liang; et al. (Journal of Hazardous Materials, 2026)

Characterisation of microbial community succession and metabolite profiles during a novel Polygonatum-fortified Liupao tea fermentation process - Junyuan Huang; Chenhao Lyu; Yilin Su; Yiqing Zhao; Zihan Qian; Wensong Sun; Jianping Chen; Lu Li; Pan Li; Bing Du (Food Bioscience, 2026)

Tailoring pore architecture in hard carbons: Clarifying the distinct sodium storage roles of closed pores and ultra-micropores - Wei-wei Kang; Hai-tao Zeng; Guang-xu Huang; Jian-bo Jia; Qiang Li; Han Hu; Bing Xu; Wei-jie Guo; Rui Hao; Bao-lin Xing; Chuan-xiang Zhang (Chemical Engineering Journal, 2026)

Structure-function relationship of polysaccharides derived from Pericarpium Citri Reticulatae 'Chachiensis': highlighting the effects on metabolic syndrome by regulating gut microbiota - Gang Huang; Bing Li; Chengguo Li; Baizhong Chen; Yapeng Li; Shuying Li; Lishe Gan; Dongli Li; Lei Chen; Chengwei He; Xueling Zhang; Ren-You Gan; et al. (Carbohydrate Polymers, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

The dual nature of neuroticism: distinct dimensions impact longevity and well-being - Yini He; Jing Xiao; Ke Hu; Tian Gao; Yan Yan; Yu Yu; Lei Wang; Kaixin Li; Wenkun Lei; Kun Zhao; Changsheng Dong; Xiaohan Tian; et al. (Science Bulletin, 2026)

Presymbiotic activation of karrikin signaling creates a permissive state for arbuscular mycorrhizal symbiosis by derepressing the NSP1–NSP2–SLR1 transcriptional complex in rice - Kai Hong; Xueying Yang; Yiqing Tan; Yonggang Liu; Qianwei Xia; Longjun Zeng; Linyuan Zou; Ke Wan; Ya Zhang; Shujing Kang; Tao Huang; Wanqing Lv; et al. (Molecular Plant, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Enhanced ligand-ligand donor-acceptor interactions via DBD plasma for MOFs with bimetallic Fe-Co active sites for H2O2 detection - Min Li; Juanjuan Geng; Bing Feng; Tianyu Luan; Xumei Tao; Liang Huang (Journal of Environmental Chemical Engineering, 2026)

Distribution pattern and development of typical antibiotic resistance genes in the continuous-flow aerobic granular sludge-membrane bioreactor system - Yongsheng Jiang; Yu Zeng; Lei Shang; Dehong Bai; Liying Bin; Weirui Chen; Xinyi Chen; Shanglong Wen; Shaosong Huang; Ping Li; Bing Tang (Journal of Environmental Chemical Engineering, 2026)

High-CH4-selectivity CO2 photoreduction enabled by in-situ constructed S-scheme Cs2CuCl4/NiAl-LDH heterojunction - Hai-bing Zhao; Yue Shu; Sheng-ning Zeng; Wen-rong Ouyang; Duo-fu Li; Hong Zhong; Wei Huang; Yan Sui (Journal of Environmental Chemical Engineering, 2026)

Modulation of gut microbiota by tangerine peel polysaccharide: A promising strategy for obesity management via acetic acid production - Chao-Yue Kong; Zhan-Ming Li; Bing Han; Yu-Qin Mao; Hui-Ling Chen; Jia-Ting Huang; Li-Shun Wang (Food Research International, 2026)

Combined exposure of enrofloxacin and disinfection byproducts under environmentally relevant concentrations enhances antibiotic resistance risks in livestock wastewater - Jin Huang; Jingjia Zhang; Uli Klümper; Jianhua Guo; Thomas U. Berendonk; Ryo Honda; Hebin Liang; Lin Lin; Xiaoyan Li; Bing Li (Water Research, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

A study on the susceptibility of Helice tientsinensis to infectious hypodermal and hematopoietic necrosis virus (IHHNV) - Meifeng Wang; Xiuhua Wang; Jie Huang; Chen Li; Qingli Zhang; Xinyu Lian; Ruoxuan Lu; Hua Xu; Xinyi Fu; Ziyue Gou; Peng Jia; Bing Yang (Journal of Invertebrate Pathology, 2026)

Diapause termination alters the m6A methylation profiles and regulates gene expression associated with early embryonic development in the silkworm (Bombyx mori) - Zhi-Hao Huang; Jia-Yue Yang; Cai-Ping Hou; Shi-Huo Liu; Bing Li; Jie Wang; Shou-jun Huang; Jia-Ping Xu (Journal of Insect Physiology, 2026)

Impact of sulfonamides on microbial community and antibiotic resistome profiles in anaerobic digestion of swine wastewater - Qinmao Zhou; Hebin Liang; Jin Huang; Uli Klümper; Peiju Fang; Zehui Yu; Yuyang Wang; Thomas U. Berendonk; Lin Lin; Xiaoyan Li; Bing Li (Journal of Hazardous Materials, 2026)

Structural and orbital multifunctional intercalation engineering of vanadium oxide for aqueous zinc-ion storage - Zi-Hang Huang; Liwen Yang; Fang-Fang Sun; Yue Zhang; Bing Tang; Fanglin Liao; Miao Liu; Ji-Chi Liu; Hui Li; Xu Han; Tianyi Ma (Chemical Engineering Journal, 2026)

Differential Bottom‐Up Control of Planktonic and Sedimentary Bacterial Communities by Phytoplankton and Extracellular Enzymes in an Asymmetric River Confluence - Yi Li; Huijuan Huang; Bi Luo; Rong Wang; Bing Yu; Xian Xu; Zhaotong Chen; Yushan Li; Zhiwei Zhu (Molecular Ecology, 2026)
Bacterial community dynamics underlie ecosystem functioning in river networks, yet how different bacterial lifestyles respond to bottom‐up biotic drivers under confluence‐induced hydraulics remains unclear. Here, we quantified spatial heterogeneity in free‐living (FL), particle‐associated (PA) and sedimentary (S) bacterial assemblages, coupled with phytoplankton and extracellular enzyme profiles, at the Yellow River‐Fenhe River confluence during the summer wet season. Clear habitat partitioning emerged, with stronger divergence at the water–sediment interface than between the two planktonic fractions (FL vs. PA). Hydrological source tracking showed that Fenhe River‐derived taxa dominated both water and sediment within the confluence reaches, whereas Yellow River lineages prevailed in the downstream reaches. Community assembly shifted hierarchically: homogeneous selection dominated FL assemblages but declined progressively toward PA and sedimentary fractions, while dispersal limitation intensified in tandem with niche contraction. Multivariate analyses showed that in addition to physicochemical factors, enzyme activity is the strongest factor predicting FL communities, explaining 43.6% of variability, whereas the phytoplankton community best predicted PA communities (68.8%). Sedimentary communities correlated weakly with phytoplankton associations (21.8%) and showed no significant link with enzyme activity. Our findings identify phytoplankton communities and enzymatic potential as key bottom‐up drivers whose relative importance varies with bacterial lifestyle, providing mechanistic insight into biophysical dynamics within river‐confluence ecosystems.

Ca2+-Independent Exocytosis Favors Axonal Release through Enlarged Fusion Pores in Sensory Neurons - Rong Huang; Xingyu Du; Qihui Wu; Yuan Wang; Yuqi Hang; Xi Wu; Yiman Li; Jie Li; Zhongjun Qiao; Yinglin Li; Lili Yin; Xiaoxuan Sun; et al. (Neuroscience Bulletin, 2026)

Histone H3.3 phosphorylation facilitates H3K9me3-heterochromatin formation during retrotransposon silencing and X-chromosome inactivation via H3.3K27me3–CBX7–KAP1 axis - Jun Chen; Jiyu Chen; Zhouliang Yu; Liwei Zhang; Yanchao Liu; Xuan Ouyang; Juan Yu; Menghan Wang; Shangqiang Xie; Ming Wang; Tiantian Zhang; Zhaohui Jin; et al. (Science Bulletin, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Metabolomic responses of free-living diazotrophs inoculated on biochar - Xinyue Li; Yi Wang; Mohammad Bahram; Yiming Xian; Rong Huang; Leho Tedersoo; Changquan Wang; Bing Li (Journal of Environmental Chemical Engineering, 2026)

Efficient degradation of dimethyl phthalate on Fenton reaction enhanced by manganese sulfide: Role of manganese and sulfur species - Ruihan Xiong; Jiasen Li; Mingjian Gao; Caixiang Zhang; Shuxin Huang; Jidao Xie; Hengyi Wang; Bing Liu (Journal of Environmental Chemical Engineering, 2026)

Single and combined impacts of antibiotics on aerobic denitrification: Cell growth characteristics and functional genes expressions - Rong-Rong Chang; Chang-Ze Shi; Yun-Jie Ruan; Bao-Cheng Huang; Ren-Cun Jin; Ming Dong; Wen-Bing Li (Journal of Environmental Sciences, 2026)

Enrichment characteristics of colloid−bound ammonium and phosphorus in groundwater systems: Insights into their sources and controls - Shuxin Huang; Mingjian Gao; Jiasen Li; Ruihan Xiong; Bing Liu; Hengyi Wang; Caixiang Zhang (Groundwater for Sustainable Development, 2026)

Plant-based egg white analogue: Curdlan-mediated crosslinking of soy and chickpea protein replicates egg white functionality - Bing Cui; Sihao Zhang; Tao Huang; Hao Li; Zidan Gong; Can Wu; Bin Zhou (Food Research International, 2026)

Cold plasma technology in food Systems: Mechanisms, multifunctional applications, and pathways to industrial adoption - Lang-Hong Wang; Haiqian Xu; Bing Yan; Boru Chen; Xin-An Zeng; Yanyan Huang; Jian Li (Food Control, 2026)

Effective elimination of malachite green from solutions by functionalized hydrochar derived from co-hydrothermal carbonization of bamboo and polyvinyl chloride with ammonium persulfate assistance - Jia-Ming Zhao; Qian Zhang; Ying-Tao Su; Xiao-Man Huang; Bing Li (Chemical Engineering Journal, 2026)

Exploring the voltage hysteresis and capacity attenuation mechanism of O2-type lithium-rich layered oxide cathodes - Chao Shen; Meng Li; Libin Hu; Zhengwei Fan; Wenkang Miao; Ronghui Hao; Xiaoyu Liu; Chang Xue; Shoushuang Huang; Qianqian Li; Bing Zhao; Yong Jiang; et al. (Chemical Engineering Journal, 2026)

Design of highly efficient and carbon-resistant catalysts for biogas reforming using entropy engineering strategy - Bing Han; Zetao Huang; Zuhao Li; Zhige Zhang; Tao Tan; Jun Xie; Yong Chen (Bioresource Technology, 2026)

Mitigation of adverse effects of calcium on struvite biomineralization for phosphorus recovery - Xingtong Chen; Yongyun Li; Yifei Ma; Bing Li; Yihe Qin; Xiaoman Li; Run Yuan; Jingjing Chen; Suran Huang; Han Li; Haiming Huang (Bioresource Technology, 2026)

Integrative approaches to river ecosystem assessment and restoration: a review of methodologies and strategies for coherent implementation - Xian-bing Zhang; Shang Huang; Yu-peng Hu; Geng Li; Wen-jie Li; Sheng-fa Yang (Environmental Monitoring and Assessment, 2026)

Performance, metabolism, and resistance of an SMX-stressed continuous-flow AGS-MBR system: Microscopic mechanism of macroscopic instability phenomena - Yu Zeng; Haowei Gao; Huiya Huang; Wenqiang Xiong; Liying Bin; Bingda Liao; Weirui Chen; Xinyi Chen; Shanglong Wen; Ping Li; Shaosong Huang; Bing Tang (Water Research, 2026)

Mechanistic insight into impacts of Cl− and Br− at high contents on phenol degradation and halogenated by-product formation in O3/H2O2 process - Bing Yang; Shijie Zhou; Xiangfu Huang; Qiang Zhou; Qinchuan Xu; Ying Qiu; Yurui Li; Mengnuo Wang; Yu Wang; Yuming Zhang; Mingyan Chen; Lili Ma; et al. (Process Safety and Environmental Protection, 2026)

Hamiltonian-system-based GRU with Fourier attention mechanism for industrial steam demand prediction - Jiasheng Li; Xian-Bing Meng; Yuxin Huang; Chengjiu Zhu; Runnan Zhang (Energy and Buildings, 2026)

Bidirectionally regulated catalytic performance of Hemin/oCNT based aptasensor via salt-induced charge screening for smartphone-assisted colorimetric detection of ATP - Tingsong Ye; Rongwei Cui; Xin Zhou; Yingying Huang; Xin Li; Sami Ramadan; Bing Li; Lizhou Xu; Danyang Li (Chemical Engineering Journal, 2026)

Corrigendum to “Gene delivery of chitosan-graft-polyethyleneimine vectors loaded on scaffolds for nerve regeneration” [Carbohydrate Polymers 290, 2022, 119499] - Yulin Wang; Ya Li; Zhongbing Huang; Bing Yang; Ning Mu; Zhaopu Yang; Min Deng; Xiaoming Liao; Guangfu Yin; Yu Nie; Tunan Chen; Hua Ma (Carbohydrate Polymers, 2026)

Statistical characteristics of storm cells and centroid-based probability nowcasts by tracking error - Kao-Shen Chung; Tsai-Jung Lee; Li-Pen Wang; Bing-Zhang Wang; Chieh-Ying Ke; Yi-Hao Tsou; Shin-Gan Chen; Ping-Yu Lin; Treng-Shi Huang (Atmospheric Research, 2026)

Identification of quantitative trait loci qPL6 for petiole length in soybean - Weiwei Fan; Lindong Wang; Wenxuan Huang; Jia Liu; Bing Li; Jingyu Peng; Ruirui Ma; Ran Xu; Lianjun Sun (Theoretical and Applied Genetics, 2026)

Subgenome Phasing Reveals the Asymmetric Evolution and Origin of the Allotetraploid Achillea wilsoniana - Wenkai Li; Dan Wang; Bing Yang; Yujia Shen; Derek W. Dunn; Xian Hai; Kang Huang; Baoguo Li (Molecular Ecology, 2026)
Allopolyploidy is an important force in plant evolution, yet studying natural allopolyploid species remains challenging due to the complexity of their genetic architecture and a lack of reference genomes. A major obstacle is the accurate phasing of subgenomes, which is a prerequisite for the application of diploid‐based population genetic tools. Here, we developed allosplitter , a novel bioinformatic tool that enables precise subgenome phasing for allotetraploids using only genotyping‐by‐sequencing (GBS) data from a derived polyploid and its diploid progenitors. We applied allosplitter to the allotetraploid Achillea wilsoniana and its progenitors ( A. acuminata and A. asiatica ). We uncovered clear asymmetric subgenome evolution: subgenome C (derived from A. acuminata ) exhibited significantly lower genetic diversity, higher population differentiation and higher Tajima's than subgenome Y (derived from A. asiatica ). This indicated a dominant evolutionary role for subgenome C, while historical introgression from A. acuminata further amplified population divergence. Phylogenetic and structure analyses enabled us to reject the biogeographic origin of A. wilsoniana in the Qinling Mountains, instead supporting its origin in the Hengduan Mountains. This study provides a reference‐genome‐free framework for polyploid genomics and offers new insights into the evolution of allopolyploids.

Development and Experimental Validation of an Ice Air Jet with a Laval Nozzle for Coal Breakage and Permeability Enhancement - Jingru Hu; Hou Zhong; Kang Cheng; Shihao Zhang; Bing Xi; Huan Li; Gensheng Li; Jingbin Li; Zhongwei Huang; Ke Hu (Rock Mechanics and Rock Engineering, 2025)

Tunable surface potential nanomaterials for enhanced environmental nucleic acid extraction and surveillance - Jiahui Lv; Tong Li; Ying Liu; Bing Li; Peng Jia; Chuwei Ma; Hongjun Xiao; Guanghui Wang; Li Cheng; Jingkai Yang; Ziyi Xu; Xuan Tan; et al. (Water Research, 2025)

Experimental and numerical study on the vortex-induced vibration of a rectangular main girder structure under coupled wind and wave action - Jiayi Han; Bing Zhu; Zhijia Li; Baojie Lu; Xianglong Huang (Ocean Engineering, 2025)

Unraveling the mechanistic interplay of carbon cycle and nitrogen transport within deep reservoirs: A perspective of δ13CDIC analysis - Yufei Bao; Yuchun Wang; Qian Zhang; Xiaobo Liu; Peng Hu; Meng Sun; Xiaodong Qu; Jie Wen; Shanze Li; Bing Lin; Jialong Huang (Journal of Hydrology, 2025)

Effects of soil labile carbon fractions and microbes on GHG emissions from flooding to drying in paddy fields - Yi Xiao; Rong Huang; Zongjin Zhang; Vanessa N.L. Wong; Xingyu Li; Xiaoyan Tang; Youlin Luo; Yingjie Wu; Jiang Liu; Shiwei Li; Changquan Wang; Bing Li (Journal of Environmental Sciences, 2025)

Sodium iron chlorophyllin-reinforced chitosan/gelatin films for fresh-cut vegetable packaging - Bing Yan; Jingyu Huang; Xiaoyu Yin; Xinyue Guan; Yingxue Tang; Jiamin Wen; Bolin Zhang; Junfeng Fan; Xiuting Li (Food Packaging and Shelf Life, 2025)

Enhanced tetracycline hydrochloride removal by ultra-microporous phosphorus-doped KOH-activated microalgal biochar: Adsorption performance and mechanistic insights - Bing Liu; Weihao Li; Yiwen Huang; Wenli Qin; Min Wang; Yang Jia; Hanqing Xu; Liyin Qu; Hongbin Jiang; Chao Wang; Zengling Ma (Environmental Research, 2025)

Pinus tabulaeformis plantations have higher drought recovery than its natural forests in the warm temperate-subtropical climate transition zone - Qin Huang; Guanjie Wang; Kun Shi; Bing Zhao; Zhenjiang Li; Xin Huang; Ting Wang; Ximei Li (Dendrochronologia, 2025)

Dual-function modifications with injected coating and lattice regulation for lithium-rich oxides towards high-stability all-solid-state batteries - Zhengwei Fan; Chao Shen; Xiaofeng Shi; Meng Li; Yiliang Huang; Libin Hu; Xiaoyu Liu; Haihua Tao; Bing Zhao; Yong Jiang; Jiujun Zhang (Chemical Engineering Journal, 2025)

Engineering Janus composite electrolytes with catalytic yolk-shell manganese oxide@C nanorods and polyimide frameworks for durable lithium-sulfur batteries - Yun-Sheng Ye; Boy-Yan Xie; Wei-Ming Huang; Jing-Yu Li; Mohamed Gamal Mohamed; Bing-Joe Hwang; Shiao-Wei Kuo (Chemical Engineering Journal, 2025)

Peripheral inflammation in spinocerebellar ataxia type 3: associations with genetic and clinical manifestations - Jia-Yi Zhang; Qiu-Ni Su; Han Lin; Wei Lin; Mao-Lin Cui; Zhuo-Ying Huang; Bei-Ning Ye; Ying-Xin Ye; Yi-Lin Jia; Qing-Ying Zhu; Zhi-Han Li; Min-Ting Lin; et al. (Inflammation Research, 2025)

Host plant effects on the non-consumptive impact of Neoseiulus bicaudus on Tetranychus turkestani - Chen Fang; Yanjie Huang; Li Zuo; Xinjie Zhang; Wurigemu Lipeizhong; Bing Zhang; Huiying Liu; Jie Su; Jianping Zhang (Experimental and Applied Acarology, 2025)

Distribution, sources, and health risks of PM2.5 and PM1-bound polycyclic aromatic hydrocarbons in the Pearl River Delta - Guang-Hong Zhai; Yue Wen; Mo Yang; Qi-Zhen Wu; Wan-Ting He; Li-Xia Liang; Le-Bing Wang; Yun-Ting Zhang; Jing-Wen Huang; Jia-Xin Zhou; Min Li; Gao Meng; et al. (Environmental Monitoring and Assessment, 2025)

Sesamol inhibits fungal growth by destroying the redox dynamic equilibrium in Pestalotiopsis neglecta - Jing-Yu Ji; Li-Ying Huang; Bing Bi; Ya-Jun Wang; Jin-Yan Zhao; Sheng-Yu Zhang; Ze Wang; Shu-ming Cui; Qiao-ya Zhang; Guo-Cai Zhang (Physiological and Molecular Plant Pathology, 2025)

Effect of different magnesium sources on tetracycline migration during struvite recovery - Lixia Qiu; Degui Gao; Chenghui Yan; Xiaofeng Wu; Wei Yu; Yuefei Huang; Bing Li (Journal of Environmental Management, 2025)

Cross-modal 2D-3D feature matching: simultaneous local feature description and detection across images and point clouds - Wei Ma; Yucheng Huang; Shengjun Tang; Xianwei Zheng; Zhen Dong; Liang Ge; Jianping Pan; Qingquan Li; Bing Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Preparation of oat metal ion chelating peptides via froth floatation: Efficacy, molecular characteristics, and their anti-browning effects - Xinyue Guan; Xixi Gao; Xiaoyu Yin; Nan Zhang; Bing Yan; Jingyu Huang; Xiangning Chen; Junfeng Fan; Xiuting Li; Bolin Zhang (Food Chemistry, 2025)

Preparation of phosphogypsum-based polysulfide and its application in solidified copper-contaminated soil - Yimo Dai; Heping Zeng; Li Duan; Jie Yang; Liping Ma; Bing Huang (Environmental Research, 2025)

Development of novel smartphone-based micro-electrochemical immunosensors for the point of care testing and typing of Helicobacter pylori in serum and whole blood - Yuhan Wang; Ping Zhang; Wei Fang; Chuxian Zhou; Gengzhou Yang; Wenwei Huang; Lijie Zhang; Xiaoli Zhang; Bing Gu; Minmin Li; Jiajie Liang; Yong Tang (Chemical Engineering Journal, 2025)

Precipitation change outweighs nitrogen addition in driving soil respiration of a saline-alkaline desert steppe - Bing Li; Xiaoyue Wang; Runsheng Ma; Hailong Yu; Juying Huang (CATENA, 2025)

Recipient Periodic Fasting Promotes Osteogenesis of Implanted Mesenchymal Stromal Cell Aggregates and Safeguards Diabetic Mandibular Bone Regeneration - Zi-Qi Zhang; Yuan Yuan; Xiao-Hui Zhang; Jia-Ning Liu; Yuan Cao; Lu Liu; Lu-Fan Yang; Yi-Han Xiao; Shan-Shan Huang; Bing-Dong Sui; Jian-Fei Liang; Ji Chen; et al. (Stem Cell Reviews and Reports, 2025)

Layered manure enhances root development via soil hydrothermal optimization in ridge tillage - Bo Kang; Xun Yan; Yingjie Zhang; Rong Huang; Youlin Luo; Qiang Xu; Lihong Han; Changquan Wang; Bing Li (Plant and Soil, 2025)

Microbial mineralization of struvite by using talc and its implications for phosphorus recovery - Xingtong Chen; Tianlei Zhao; Bing Li; Yihe Qin; Xiaoman Li; Run Yuan; Jingjing Chen; Han Li; Haiming Huang (Applied Clay Science, 2025)

Advances in Selective Recovery and Resource Utilization of Iron, Manganese and Copper from Acid Mine Drainage - Xinyi Liu; Yahui Liu; Xinrui Huang; Xinrui Zhong; Renjie Li; Guo Liu; Bing Liao (Current Pollution Reports, 2025)

New lignans from Phyllanthodendron dunnianum - Li Xu; Jian-Bing Tan; Yu-Ting Zheng; Zi-Huan Sang; Si-Yu Qin; Yuan-Tao Huang; Mei-Fang Li; Zhen-Xing Zou (Natural Product Research, 2025)

The application of manure and straw is beneficial for improving the content and stability of DOM in paddy soil - Qinghua Zhou; Jiayue Zhou; Weiliang Xiong; Shiwei Li; Ouping Deng; Yi Xiao; Xingyu Li; Bing Li; Changquan Wang; Xuesong Gao; Genchuan Bai; Jiang Liu; et al. (Journal of Environmental Management, 2025)

Z-scheme Cu2O/g-C3N4/Ag heterostructures: A novel approach for simultaneous water pollutant removal and real-time SERS monitoring - Kaiyue Li; Wenhui Li; Ping Huang; Yuquan Zhuo; Ziwen Yang; Bo Wang; Runru Liu; Bing Liu; Enzhu Hou; Shuo Yang; Donglai Han (Journal of Environmental Chemical Engineering, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

UV/green rust/glucose oxidase-based Fenton-like Systems for algal removal: Mechanisms of sustained oxidative capacity in UV-enhanced systems - Siwei Li; Qian Zhang; Meng Li; Xiangyu Liu; Jie Peng; Bing Lin; Jialong Huang; Yong Huang (Journal of Environmental Chemical Engineering, 2025)

Sustainable treatment of hazardous wastewater and carbon sequestration: Zn-doped δ-MnO2 catalyzed humification of toxic DOM and pollutant removal - Chao Zhu; Yiruo Huang; Ze Ding; Jinsong Xu; Mengnan Wang; Bing Yang; Hongrui Ma; Chengtao Li (Journal of Environmental Chemical Engineering, 2025)

Reborn from fertilizer to fire safety: Development of effective gel flame retardants using recovered phosphorus from wastewater - Chenghui Yan; Bing Li; Lixia Qiu; Jingfu Chen; Jingsi Gao; Muhammad Tajammal Munir; Xiaofeng Wu; Wei Yu; Yuefei Huang (Journal of Environmental Chemical Engineering, 2025)

Enhanced aerobic granular sludge cultivation in continuous-flow membrane bioreactors: Evaluating a novel vertical circulation configuration and multi-mechanism approach - Tenglong Dai; Mengci Ni; Liying Bin; Weirui Chen; Ping Li; Xinyi Chen; Shanglong Wen; Shaosong Huang; Bing Tang (Journal of Environmental Chemical Engineering, 2025)

Soil organic and inorganic carbon pools in the Loess Plateau: New estimation, change and trade-offs - Jianzhao Wu; Lei Deng; Yakov Kuzyakov; Yuanyuan Huang; Xiaodong Song; Ming Nie; Jianming Deng; Peng Zhao; Yang Liao; Lingbo Dong; Xiaozhen Wang; Jiwei Li; et al. (Global and Planetary Change, 2025)

Comb-shaped cationic bridges in phosphoric acid-doped PBI gel membranes: A pathway to flexible and efficient fuel cell operation from −20 °C to 200 °C - Chao Chen; Yan Chen; Bing Zhao; Mingjie Ma; Ningbo Wang; Zheng Li; Yunchu Cheng; Ling Zhou; Congjie Gao; Fei Huang; Lixin Xue (Chemical Engineering Journal, 2025)

Metagenomics-metabolomics integration reveals the impacts and action mechanisms of sulfamethoxazole in a continuous-flow aerobic granular sludge membrane bioreactor: System performance and microbial functional shifts - Wenqiang Xiong; Yu Zeng; Liying Bin; Weirui Chen; Xinyi Chen; Shanglong Wen; Shaosong Huang; Ping Li; Bing Tang (Chemical Engineering Journal, 2025)

Structural and electronic regulation of thienothiophene-based covalent organic frameworks for enhanced photocatalytic oxidative coupling activity of amines - Xiaoping Tan; Enyuan Ao; Enling Zhou; Xinyao Zha; Mingyu Li; Fulan Zhang; Bingfang Yuan; Quan Gou; Bing Li; Huisheng Huang; Genfu Zhao (Chemical Engineering Journal, 2025)

Dynamic color-tunable luminescence in lead-free perovskites by asymmetric energy transfer and excitation-dependent dual self-trapped excitons emission - Qinghua Li; Feifei Ma; Xiaoqing Peng; Tianfu Gao; Bing Xu; Lanting Huang; Jinke Bai; Qingping Li; Weifeng Zhao (Chemical Engineering Journal, 2025)

Multifunctional integrated separator based on electrospinning structure engineering for high-stability lithium sulfur batteries - Chaojiang Fan; Rong Yang; Bing Chen; Qing Huang; Lingjiang Kou; Jiajia Song; Yong Wang; Teng Wang; Yinglin Yan; Zhongguo Zhao; Kai Jia; Wenhu Li; et al. (Chemical Engineering Journal, 2025)

Harnessing nanomaterial-driven electron transfer for enhanced uranium recovery and toxicity mitigation in bioelectrochemical systems - Meng Li; Leyi Chen; Kengqiang Zhong; Haowen He; Xing Chen; Xing Lu; Chengjun Guo; Luoyi Han; Ziyin Xia; Chenxi Li; Jingyi Wang; Wei Han; et al. (Bioresource Technology, 2025)

Multi-omics analysis revealed the addiction to glutamine and susceptibility to de novo lipogenesis of endometrial neoplasm - Yuemeng Zhu; Yingxin Zheng; Qing Zhang; Leshi Chen; Yitong Ouyang; Zhiqiang Song; Bing Zhao; Chao Gu; Beihua Kong; He Huang; Jin Li (Science China Life Sciences, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Enhanced mapping of essential urban land use categories in China (EULUC-China 2.0): integrating multimodal deep learning with multisource geospatial data - Ziming Li; Bin Chen; Yufei Huang; Han Wang; Yadian Wang; Yiming Yuan; Xuecao Li; Jing M. Chen; Bing Xu; Peng Gong (Science Bulletin, 2025)

Cadmium and rising tides: Amplified greenhouse gas emissions from mangrove sediment - Hengzhi Yin; Ruili Li; Xiaofeng Wu; Yuefei Huang; Guanghui Lin; Bing Li; Guanqian Wang (Regional Studies in Marine Science, 2025)

Insights into bridging hydroxyl groups to enhance the efficient-generation of hydroxyl radicals for microplastic decomposition - Zehao Li; Boqiang Gao; Shuanglong Ma; Kai Wang; Jingyi Wei; Shengjun Xu; Yan Huang; Jia Song; Xiaodan Tang; Jingzhen Wang; Sihui Zhan; Bing-Jie Ni (Journal of Cleaner Production, 2025)

Legume‑based rotation increases soil phosphorus availability and enhances subsequent crop yields - Zhen Chen; Xin Wang; Shou-Bing Huang; Sebastian Munz; Simone Graeff-Hönninger; Jens Hartung; Xiao-Gui Liang; Si Shen; Shun-Li Zhou (European Journal of Agronomy, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

Extracellular vesicles in antimicrobial therapy: Advances, challenges and perspectives - Rongjia Han; Weiwei Wang; Yaxin Zhou; Bing Li; Rongbin Hu; Jingru Zuo; Jiabao Xing; Hongxing Zhang; Huan Huang; Yubin Bai; Jiyu Zhang (Chemical Engineering Journal, 2025)

A Novel Phosphorus-Recovering Bacterium Pelagibacterium mangrovi sp. nov., Isolated from Mangrove Sediment - Shang Yang; Guohong Liu; Ruili Li; Wei Yu; Yuefei Huang; Xiaofeng Wu; Shungui Zhou; Bing Li (Current Microbiology, 2025)

Light-driven biohybrid for phosphorus recovery via struvite biomineralization in tetracycline-laden livestock wastewater - Shang Yang; Andong Hu; Jia Zhang; Wei Yu; Xiaofeng Wu; Yuefei Huang; Shungui Zhou; Bing Li; Guangqian Wang (Water Research, 2025)

Micropatterned piezoelectric films induced by modulated corona field for weak signal detection - Fu Lv; Chenghang Yu; Bing Liu; Jiamin Lin; Zijian Hong; Yongjun Wu; Zhaohui Ren; Qilong Zhang; Shurong Dong; Jikui Luo; Juan Li; Yuhui Huang (Chemical Engineering Journal, 2025)

Genetic mutations across multiple pathways drive filamentous growth and virulence in the emerging fungal pathogen Candida auris - Chao Li; Shuaihu Li; Qiushi Zheng; Li Tao; Jian Bing; Zhangyue Guan; Tianren Hu; Haiqing Chu; Guanghua Huang (Science China Life Sciences, 2025)

An Automated Framework for Probabilistic Back-Analysis of Rockfall Catalogs Using Bayesian Optimization and Radar Tracking - Arnold Yuxuan Xie; Zhanyu Huang; Bing Q. Li (Rock Mechanics and Rock Engineering, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Research progress on electrochemiluminescence nanomaterials and their applications in biosensors - A review - Ming-Zhu Deng; Ming-Yu Zhong; Meng-Li Li; Gui-Qun Huang; Hao He; Xiao Xiao; Ruo-Bing Bai; Ruchika Hansanie Ukwatta; Li Mi; Ting-Ting Zhang; Yong-Hong Hu; Hui-Cheng Shi; et al. (Analytica Chimica Acta, 2025)

Aging influences protein digestion, absorption and amino acid metabolism - Lili Qiu; Qianqian Huang; Wenhao Li; Qian Zhang; Jun Zhou; Juan Chen; Yixuan Li; Ran Wang; Pengjie Wang; Siyuan Liu; Bing Fang; Xiaoyu Wang (Biogerontology, 2025)

Black Soldier Fly Larvae Meal as a Sustainable Fishmeal Substitute for Juvenile Hybrid Grouper: Impacts on Growth, Immunity, and Gut Health - Yan Chen; Wenfeng Li; Minyi Zhong; Jun Ma; Bing Chen; Junming Cao; Jiun-Yan Loh; Hai Huang (Fishes, 2025)
Background: Aquaculture increasingly seeks sustainable alternatives to fishmeal, a key protein source in fish diets. Black Soldier Fly Larvae (BSFL) meal is a promising substitute, but its effects on fish growth, immunity, and gut health need further investigation. This study aimed to evaluate the impact of varying BSFL inclusion levels on juvenile hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂), a widely farmed species in tropical aquaculture. Methods: Juvenile hybrid grouper were fed diets with four levels of BSFL substitution (0%, 10%, 30%, and 50%) over 56 days. Key metrics such as growth performance, immune function, antioxidant capacity, and gut transcriptome were analyzed. Results: Replacing fish meal with BSFL meal had no significant effect on the survival rate of hybrid grouper (p > 0.05) but significantly affected growth performance, immune function, and antioxidant capacity (p

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

Eco-resilience of China's mangrove wetlands: The impact of heavy metal pollution and dynamics - Shafeeq Ur Rahman; Jing-Cheng Han; Yang Zhou; Bing Li; Yuefei Huang; Ali Farman; Xu Zhao; Luqman Riaz; Ghulam Yasin; Sami Ullah (Environmental Research, 2025)

Rock moisture dynamics in sandstone caves responsible for weathering: Field observations and numerical modeling - Ran Niu; Xiao-Wei Jiang; Kaigao Ouyang; Xi Yang; Xu-Sheng Wang; Ji-Zhong Huang; Hong-Bing Yan; Li Wan (Engineering Geology, 2025)

An interpretable spatially weighted machine learning approach for revealing spatial nonstationarity impacts of the built environment on air pollution - Shumin Wang; Mingxing Hu; Jianyu Li; Guoao Liu; Wanqi Hu; Junheng Qi; Jingyue Huang; Ziye Liu; Hui Wang; Bing Han (Building and Environment, 2025)

Unlocking interfacial electron transfer in biophotoelectrochemical processes: Role of extracellular polymeric substances in aquatic environments - Andong Hu; Bing Li; Shang Yang; Chaohui Yang; Jie Ye; Yuefei Huang; Shungui Zhou; Guangqian Wang (Water Research, 2025)

Chemical constituents from the stems of Erythropalum scandens - Qiao-dan Pan; Yuan-he Huang; Li-yang Zhao; Wei-rui Wang; Bing-an Wei; Ying-ying Xu; Xian Wei (Phytochemistry Letters, 2025)

Co-occurrence and co-expression of antibiotic, biocide, and metal resistance genes with mobile genetic elements in microbial communities subjected to long-term antibiotic pressure: Novel insights from metagenomics and metatranscriptomics - Jiayu Zhang; Huaxin Lei; Jin Huang; Jonathan W.C. Wong; Bing Li (Journal of Hazardous Materials, 2025)

Functional materials based on kitchen waste fermentation residue for the remediation of cadmium-contaminated soil - Xiaohui Zhu; Zhexuan Li; Tianyu Gu; Ruiying Wang; Junxin Yu; Weiming Zhu; Li Jiang; Ying Huang; Bing Li; Zhiying Dong (Journal of Environmental Chemical Engineering, 2025)

Identification and validation of mitochondrial endoplasmic reticulum membrane-related genes in atherosclerosis - Li-Rong Wang; Chun-Xi Zhang; Lv-Bo Tian; Jie Huang; Li-Jun Jia; Hao Tao; Neng-Wei Yu; Bing-Hu Li (Mammalian Genome, 2025)

Biochar derived from feedstock with high lignin content leads to better soil improvement performance in red soils: from the perspective of soil microbial regulation and carbon stabilization - Bowei Lv; Bing Ma; Yulong Li; Li Wu; Min Huang; Xiaoman He; Jianming Xue; Lie Yang (Environmental Geochemistry and Health, 2025)

Design and Experiment of a Hard-Shell Clam Harvester - Haiyun Wu; Xiaomeng Wang; Bing Huang; Shide Li; Jincheng Hu; Shancan Fu; Lei Yang; Mengxiang Cui; Zhenwei Chen; Yanan Zeng; Yongcheng Jiang; Tao Zhang (Fishes, 2025)
Hard-shell clams are highly valued for their nutritional and economic benefits, leading to an increase in their aquaculture scale. Harvesting these clams manually leads to low efficiency and high labor intensity; thus, a new type of hard-shell clam harvester has been designed to overcome this challenge. Based on biological characteristics and sediment properties of hard-shell clams, a 3D model of the harvester has been created utilizing SolidWorks software (version 2022), which has a working length of 980 mm, an excavation depth range from 0~12 mm, and an angle of entry of 22 degrees. To optimize the efficiency of the machine, a Discrete Element Method (DEM) simulation trial was conducted through a three-factor three-level experiment using EDEM software. Results indicated an optimal harvest efficiency of 91.17% with the machine achieving a running speed of 0.526 m/s, roller speed of 4.772 r/min, and excavation depth of 73.067 mm. Field experiments verified the feasibility of the harvester, demonstrating high accuracy when compared to simulation results.

Organic fertilizer intensifies the vertical heterogeneity of DOM in paddy fields through interactions with soil minerals - Yi Xiao; Rong Huang; Weiliang Xiong; Binbin Liu; Qinghua Zhou; Tao Jiang; Vanessa N.L. Wong; Jiang Liu; Yingjie Wu; Youlin Luo; Qiquan Li; Qiang Xu; et al. (Soil and Tillage Research, 2025)

The mechanisms of salt weathering responsible for sandstone deterioration in the Yungang Grottoes, China - Xi Yang; Xiao-Wei Jiang; Kai-Gao Ouyang; Tao-Tao Ji; Yi-Fan Gao; Xiao-Hong Geng; Ran Niu; Ji-Zhong Huang; Hong-Bing Yan; Li Wan (Engineering Geology, 2025)

A TaqMan ‐ MGB Probe Quantitative PCR Assay Detecting Hematodinium perezi - Guosi Xie; Hailiang Wang; Mengting Zhu; Jingnan Bi; Liuxin Yang; Xiaoyuan Wan; Meng Li; Enpei Xie; Chengyin Shi; Bing Yang; Qingli Zhang; Caiwen Li; et al. (Journal of Fish Diseases, 2025)
Hematodinium perezi , a pathogenic dinoflagellate, is one of major epidemiological agents that lead to severe losses of cultured marine crustaceans in China. This study aimed to develop a novel, sensitive and specific detection method qualified for early surveillance and control of the disease caused by H. perezi . The present study established a TaqMan‐MGB probe quantitative PCR (qPCR) method, targeting the first internal transcribed spacer 1 (ITS 1) region of H. perezi by optimising reaction components. A high correlation coefficient ( R 2 = 0.9996) was obtained in a standard curve with a 103.4% efficiency. No amplification was observed for the host's genome and pathogens other than H. perezi in the TaqMan‐MGB probe qPCR assays, showing high specificity to H. perezi . When using the plasmid standard DNA as templates, the detection limit of the qPCR method was determined to be 5.66 copies/reaction and 10 times more sensitive than the conventional PCR. The TaqMan‐MGB probe qPCR assays exhibited high repeatability, and the intra‐ and inter‐assay coefficients of variation (CV) ranged from 0.11% to 2.25% over a wide dynamic range of detection from 5.66 × 10 0 to 5.66 × 10 9 copies of targeting gene. The application was also validated on clinical samples, including those with low infection with H. perezi . This novel one‐step TaqMan‐MGB probe qPCR provides an option for surveillance and epidemiological investigations of H. perezi infection, with an advantage at the early infection stage.

A new sesquiterpene from endophytic fungus Colletotrichum sp. B-89 - Ke-tao Zhang; Bing Zhang; Zhi-pu Huang; Yu-xiao Xu; Xiao-rong Xu; Si-heng Li; Qing Zhao; Xiao-mei Zhang (Natural Product Research, 2025)

MiR-518b Promotes the Tumorigenesis of Hepatocellular Carcinoma by Targeting EGR1 to Regulate PI3K/AKT/mTOR Signaling Pathway - Xinyuan Wang; Juan Li; Jiao Nong; Xin Deng; Yiping Chen; Bing Han; Lin Zeng; Xiabing Huang (Cell Biochemistry and Biophysics, 2025)

Three new metabolites from the endophyte Fusarium proliferatum T2-10 - Jian-Bing Tan; Wei-Wei Peng; Mei-Fang Li; Feng-Hua Kang; Yu-Ting Zheng; Li Xu; Si-Yu Qin; Yuan-Tao Huang; Zhen-Xing Zou (Natural Product Research, 2025)

Phosphorus recovery and reuse: Innovating with biochar in the circular economy - Yuxin Wang; Tajammal Munir; Xiaofeng Wu; Yuefei Huang; Bing Li (Science of The Total Environment, 2025)

UV activated peroxymonosulfate synergistically removes Microcystis aeruginosa and Chlorella vulgaris - Huixin Li; Yu Luo; Min-Yong Lee; Hao Shen; Sisi Li; Hong Chen; Yanfei Zhou; Bingyu He; Bing Xie; Huan He; Xuejun Pan; Guohua Dao; et al. (Journal of Environmental Chemical Engineering, 2025)

Ultra-fast preparing carbon nanotube-supported Ni-Fe bimetallic compounds as robust electrocatalysts for oxygen evolution reaction - Taotao Gao; Qi An; Shumin Yu; Xiangrui Feng; Bing Li; Yanyan Huang; Hai Lan; Dan Xiao (Fuel, 2025)

Probiotic-fermented ginger-processed Gastrodia elata BI. Ameliorates AlCl3-induced cognitive dysfunction in an Alzheimer's disease rat model by regulating the gut microbiota and CREB/BDNF pathway - Junyuan Huang; Lanyu Lai; Yilin Su; Jianping Chen; Pan Li; Bing Du (Food Research International, 2025)

Unveiling the secrets of the bistability of aerobic granular sludge in a continuous flow membrane bioreactor for treating real municipal wastewater - Biao Yang; Liying Bin; Weirui Chen; Xinyi Chen; Ping Li; Shanglong Wen; Shaosong Huang; Zhiqi Zhang; Bing Tang (Chemical Engineering Journal, 2025)

A mini review of Liparis species: an ornamental genus with considerable medicinal value - Xiao-Bing Chen; Li-Yun Huang; Min Zhou; Zhi-Jie Ling; Yan-Ping Liu; Xi-Lin Ouyang (Natural Product Research, 2025)

The truncation effect of soil slope acceleration responses - Yu-Bing Wang; Xiao-Shi Huang; Chao Li (Soil Dynamics and Earthquake Engineering, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Phylogenomics of Paragymnopteris (Cheilanthoideae, Pteridaceae): Insights from plastome, mitochondrial, and nuclear datasets - Jing Zhao; Zhen-Long Liang; Shao-Li Fang; Rong-Juan Li; Chuan-Jie Huang; Li-Bing Zhang; Tanner Robison; Zhang-Ming Zhu; Wen-Jing Cai; Hong Yu; Zhao-Rong He; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2025)

Antitussive drug dextromethorphan induces developmental impairment in zebrafish - Dong-Dong Ma; Wen-Jun Shi; Zhi-Jie Lu; Jin-Ge Zhang; Li-Xin Hu; Zheng Huang; Si-Ying Li; Xiao-Bing Long; Xin Liu; Chu-Shu Huang; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Transforming behavior and removal mechanism of phosphorus from municipal wastewater in a continuous flow aerobic granular sludge-membrane bioreactor: Unveiling the functional genes associated with phosphorus metabolism - Bingduo Wang; Mengci Ni; Yu Zeng; Biao Yang; Lei Shang; Liying Bin; Weirui Chen; Ping Li; Xinyi Chen; Shanglong Wen; Shaosong Huang; Bing Tang (Chemical Engineering Journal, 2025)

Development of an oral vaccine delivery system for shrimp aquaculture using attenuated Listeria monocytogenes - Jeff Chia-Kai Hsu; Te-Ken Hsu; Shuh-Bing Guan; Po-Wei Chi; Chih-Ying Chiang; Colin William Pouton; Zi-Wey Wong; Po-Yu Huang; Li-Li Chen (Aquaculture, 2025)

A plant growth-promoting bacterium supports cadmium detoxification of rice by inducing phenylpropanoid and flavonoid biosynthesis - Yingjie Wu; Haiyang Zhao; Meijuan Xiao; Huimin Liu; Hua He; Lu Peng; Qi Tao; Xiaoyan Tang; Yanyan Zhang; Rong Huang; Bing Li; Changquan Wang (Journal of Hazardous Materials, 2025)

Evaluation of the shear stability of aerobic granular sludge from a pilot-scale membrane bioreactor: Establishment of a quantitative method - Biao Yang; Bingduo Wang; Liying Bin; Weirui Chen; Xinyi Chen; Ping Li; Shanglong Wen; Shaosong Huang; Zhiqi Zhang; Bing Tang (Journal of Environmental Sciences, 2025)

Numerical and experimental study of the combustion performance of an integrated inclined combustor - Bing Huang; Wei Li; Xu Yang; Yunpeng Liu; Yingwen Yan (Fuel, 2025)

Biogenic amines degradation ability of Saccharomyces cerevisiae I45 and Pichia sp. NW5 & LB60 and their application in beer fermentation - Kexin Hong; Chenyu Li; Jingya Ai; Xiaoyu Han; Bing Han; Qiuxing Qin; Huan Deng; Tianyang Wu; Xiaoxuan Zhao; Weidong Huang; Jicheng Zhan; Yilin You (Food Research International, 2025)

Dumbbell-like AuNRs/CeO2 hybrid catalyst with near-infrared boosted peroxidase-like activity for colorimetric sensing of acetylcholinesterase - Bing Wang; Yurou Huang; Fengxian Zhang; Jinyu Wang; Ke Wang; Cao Li; Zhenpeng Qiu; Xiaoying Wang; Ziqiang Xu (Chemical Engineering Journal, 2025)

Insights into the formation and development of membrane fouling in a continuous flow aerobic granular sludge membrane bioreactor - Mengci Ni; Juan Jiang; Biao Yang; Bingduo Wang; Liying Bin; Weirui Chen; Ping Li; Shaosong Huang; Bing Tang (Chemical Engineering Journal, 2025)

Non-metal iodine single-atom catalysts anchored on N-doped graphene for high-performance lithium-sulfur battery - Xue Li; Jiaqi Yu; Wenzhuo Li; Yalan Liao; Meng Li; Bing Zhao; Xiaoyu Liu; Shoushuang Huang; Shuixin Xia; Jiujun Zhang; Yong Jiang (Chemical Engineering Journal, 2025)

Efficient transformation of starch food wastes into bio-based levulinate products over earth-abundant aluminum salts: Performances and economics - Ke-Ming Li; Jia-Yue Chen; Yao Xiao; Feng-Shuo Guo; Yao-Bing Huang; Qiang Lu (Biomass and Bioenergy, 2025)

Foodborne iron overload induces oxidative stress and causes mitochondrial damage in the liver of grass carp (Ctenopharyngodon idellus) - Xiaoman Huang; Yan Yang; Yanhan Bai; Shiyi Yang; Bing Chen; Linpeng Zhang; Lihan Liu; Junjie Tao; Chengming Tu; Li Lin; Zhendong Qin (Aquaculture, 2025)

Unveiling the neglected impacts of halide ions on phenol removal in UV/H2O2 system: Light shielding and oxidant utilization efficiency - Bing Yang; Ying Qiu; Qiuping Luo; Xiangfu Huang; Yurui Li; Shijie Zhou; Mengnuo Wang; Mingyan Chen; Lili Ma; Lingli Li; Yucheng Liu (Journal of Water Process Engineering, 2025)

Ultrafiltration membrane fouling of microalgae-derived intracellular organic matter exposed to pharmaceuticals and personal care products (PPCPs) - Weiwei Huang; Hongkai Xu; Lei Yao; Tian Li; Yongting Qiu; Hongjian Yu; Huan He; Chunzhong Wei; Junxia Liu; Wenzong Zhou; Bingzhi Dong; Bing Wu (Journal of Water Process Engineering, 2025)

A cell-based exploration of environmental and health impacts of food waste digestate for its sustainable reutilization - Xiujiao Pan; Qingmeng Liu; Yukun Wang; Mingshuai Shao; Yongyi Wei; Xin Li; Miao Huang; Lianghong Cheng; Qiyong Xu; Xiaoxia Zhou; Bing Yan (Journal of Environmental Management, 2025)

Harnessing metal-metal interactions for simultaneously boosting photocatalytic hydrogen and benzaldehyde production - Yajie Feng; Chi Lin; Yifei Huang; Bing Li; Yingxin He; Jiangping Ma; Chaogang Ban; Lujie Ruan; Hongxing Jia; Xiaoping Tao; Liyong Gan; Xiaoyuan Zhou (Chemical Engineering Journal, 2025)

A hydro-stable and phase-transition-free P2-type cathode with superior cycling stability for high-voltage sodium-ion batteries - Jun Xiao; Hong Gao; Yang Xiao; Shijian Wang; Cheng Gong; Zefu Huang; Bing Sun; Chung-Li Dong; Xin Guo; Hao Liu; Guoxiu Wang (Chemical Engineering Journal, 2025)

In situ reactivation of aerobic granular sludge in a membrane bioreactor after long-term storage: Revealing the variation in metabolic pathways under restored bioactivity - Yu Zeng; Bingduo Wang; Liying Bin; Weirui Chen; Ping Li; Xinyi Chen; Shanglong Wen; Shaosong Huang; Bing Tang (Chemical Engineering Journal, 2025)

Quinacridone derivative as a thickness-insensitive cathode interlayer for efficient and stable inverted perovskite solar cells - Zilong Bing; Chengzhuo Yu; Jialin Yang; Huiru Liu; Weiping Chen; Jingsong Huang; Fenghong Li (Chemical Engineering Journal, 2025)

Exosome-anchored scholzite conversion coating on titanium with long-term stability and immunomodulatory ability to enhance osteogenesis - Shimin Dai; Benzhao Huang; Peng Wang; Xiaoqing Lu; Shishuo Li; Zhibo Zhao; Xiao Li; Ningbo Li; Jiahui Yu; Zhentao Man; Wei Li; Bing Liu (Chemical Engineering Journal, 2025)

Effects of olanzapine in the improvement of body weight and appetite in patients with cancer or receiving chemotherapy: a systematic review and meta-analysis - Lu Yuan; Xin-Yu Li; Lu Xu; Si-Jie Quan; Yan-Bing Huang; Hui Zheng (European Journal of Clinical Pharmacology, 2025)

Heavy metal emissions from on-road vehicles in Xia-Zhang-Quan metropolitan area in southeastern China from 2015 to 2060: impact of vehicle electrification - Zhe-Nan Wen; Qi-Yu Miao; Jiang-Ru Chen; Shui-Ping Wu; Li-Xiong He; Bing-Qi Jiang; Yi-Jing Liu; Zhi Huang (Environmental Science and Pollution Research, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Exploring the impact of visible light intensity on algae-bacterial symbiotic system treating aniline wastewater: Performance, microbial community and metabolic pathways - Jiajing Chen; Qian Zhang; Meng Li; Jing He; Bing Lin; Nanping Wu; Xunhao Liu; Siwei Li; Jialong Huang; Xiaoqian Dong; Hongyu Wang (Journal of Water Process Engineering, 2024)

Phosphorus deficiency promotes root:shoot ratio and carbon accumulation via modulating sucrose utilization in maize - Zu-Dong Xiao; Zhen-Yuan Chen; Yi-Hsuan Lin; Xiao-Gui Liang; Xin Wang; Shou-Bing Huang; Sebastian Munz; Simone Graeff-Hönninger; Si Shen; Shun-Li Zhou (Journal of Plant Physiology, 2024)

The effects of small plastic particles on antibiotic resistance gene transfer revealed by single cell and community level analysis - Yuqiu Luo; Tiansi Xu; Bing Li; Fan Liu; Beibei Wu; Phil S. Dobson; Huabing Yin; Zheng Chen; Yong Qiu; Xia Huang (Journal of Hazardous Materials, 2024)

Seawater boosts oxytetracycline (OTC) residues in struvite via hydroxyapatite (HAP) and dissolved organic matter (DOM) co-precipitation - Degui Gao; Yuefei Huang; Shungui Zhou; Bing Li; Guangqian Wang (Journal of Hazardous Materials, 2024)

Charge density-mediated crystallization kinetics for SSZ-13 transformed from coal fly ash-derived Al-rich analcite - Xiangyu Li; Bing Wang; Xiang Liao; Ruiqi Yin; Weiguo Ren; Liping Chang; Weiren Bao; Wenju Wang; Zhanggen Huang; Lina Han; Jiancheng Wang (Journal of Environmental Chemical Engineering, 2024)

Ameliorative effects of Trichosanthes kirilowii Maxim. seed oil on hyperlipidemia rats associated with the regulation of gut microbiology and metabolomics - Weili Chen; Zhangbao Zhou; Ruida Qi; Jun Zhou; Huiying Liang; Pinxi Huang; Zebin Zou; Ling Dong; Hua Li; Bing Du; Pan Li (Food Research International, 2024)

Natural pigments in the food industry: Enhancing stability, nutritional benefits, and gut microbiome health - Zhi-Hong Zhang; Jialin Chen; Xin Huang; Rana Muhammad Aadil; Bing Li; Xianli Gao (Food Chemistry, 2024)

Widely targeted metabolomics and flavoromics reveal the effect of Wickerhamomyces anomalus fermentation on the volatile and nonvolatile metabolites of black garlic juice - Yan-Bing Huang; Fan-Bing Meng; Chuan-Xian Gong; Yun Deng; Yun-Cheng Li; Li-Shi Jiang; Yu Zhong (Food Chemistry, 2024)

Glucose-induced glycation enhances the foaming properties of Trichosanthes kirilowii seed protein isolate: Insights into structure, interfacial behavior, and proteomics - Dong Peng; Weijuan Huang; Hanxiao Bao; Wanyue Ding; Xiangmin Pan; Guosen Li; Ling Dong; Weiwen Li; Jianping Chen; Pan Li; Bing Du (Food Hydrocolloids, 2024)

Single-cell transcriptome analysis of the mouse lungs during the injury and recovery periods after lipopolysaccharide administration - Hou-Ping Wang; Jian He; Jian-Rong He; Dan-Dan Li; He Huang; Bing Chen (Inflammation Research, 2024)

Analysis of deliquescent chloride salt by laser-induced breakdown spectroscopy with controlled uniform precipitation - Lizhu Kang; Ji Chen; Zhijie Huang; Zhanjian Lin; Rui Zhang; Bing Lu; Xiangyou Li (Analytica Chimica Acta, 2024)

Jeotgalibacillus haloalkalitolerans sp. nov., a novel alkalitolerant and halotolerant bacterium, isolated from the confluence of the Fenhe River and the Yellow River - Ya-Fei Zhang; Yun-Lin Peng; Yong-Hui Xiao; Bing Yu; Ming-Yue Cao; Zhi-Ling Zhang; Le-Qun Huang; Yi Li (Antonie van Leeuwenhoek, 2024)

Decrypting the viral community in aerobic activated sludge reactors treating antibiotic production wastewater - Aixi Tang; Jiayu Zhang; Jin Huang; Yu Deng; Dou Wang; Pingfeng Yu; Renxin Zhao; Yulin Wang; Zihan Chen; Tong Zhang; Bing Li (Water Research, 2024)

Robust polymer electrolytes with fast ion-transport nanochannels constructed by carbon dots for long lifespan Li metal batteries - Jia-Wen Ni; Xi-Rong Zhang; Tian-Bing Song; Zun-Hui Huang; Qian-Li Ma; Tian-Le He; Huan-Ming Xiong (Chemical Engineering Journal, 2024)

Photoelectrochemical methane production achieved energy recovery from wastewater with low organic concentration - Andong Hu; Tao Fu; Jie Ye; Yuefei Huang; Shungui Zhou; Bing Li; Guangqian Wang (Chemical Engineering Journal, 2024)

Nucleus Accumbens Corticotropin-Releasing Hormone Neurons Projecting to the Bed Nucleus of the Stria Terminalis Promote Wakefulness and Positive Affective State - Gaojie Pan; Bing Zhao; Mutian Zhang; Yanan Guo; Yuhua Yan; Dan Dai; Xiaoxi Zhang; Hui Yang; Jinfei Ni; Zhili Huang; Xia Li; Shumin Duan (Neuroscience Bulletin, 2024)
The nucleus accumbens (NAc) plays an important role in various emotional and motivational behaviors that rely on heightened wakefulness. However, the neural mechanisms underlying the relationship between arousal and emotion regulation in NAc remain unclear. Here, we investigated the roles of a specific subset of inhibitory corticotropin-releasing hormone neurons in the NAc (NAc CRH ) in regulating arousal and emotional behaviors in mice. We found an increased activity of NAc CRH neurons during wakefulness and rewarding stimulation. Activation of NAc CRH neurons converts NREM or REM sleep to wakefulness, while inhibition of these neurons attenuates wakefulness. Remarkably, activation of NAc CRH neurons induces a place preference response (PPR) and decreased basal anxiety level, whereas their inactivation induces a place aversion response and anxious state. NAc CRH neurons are identified as the major NAc projection neurons to the bed nucleus of the stria terminalis (BNST). Furthermore, activation of the NAc CRH -BNST pathway similarly induced wakefulness and positive emotional behaviors. Taken together, we identified a basal forebrain CRH pathway that promotes the arousal associated with positive affective states.

Preparation and characterization of biochar from four different solid wastes and its ampicillin adsorption performance - Junxin Yu; Tianyu Gu; Ruiying Wang; Bing Li; Zhiying Dong; Xiaohui Zhu; Zhexuan Li; Tiantian Hu; Ying Huang (Environmental Geochemistry and Health, 2024)

Acinetobacter corruptisaponis sp. nov., Isolated from a Spoiled Bath Lotion - Ying-Si Wang; Gang Zhou; Hong-Bing Tao; Lei Gao; Bao-Zhu Fang; Xiu-Jiang Yang; Hong Peng; Xia Wen; Xiao-Mo Huang; Jie Wang; Wen-Jun Li; Qing-Shan Shi; et al. (Current Microbiology, 2024)

Sirt4 Overexpression Modulates the JAK2/STAT3 and PI3K/AKT/mTOR Axes to Alleviate Sepsis-Induced Acute Lung Injury - Cancan Xie; Ting Wang; Anmin Liu; Bing Huang; Weizhong Zeng; Zhengrong Li; Suna Peng; Shuanghua Wu (Cell Biochemistry and Biophysics, 2024)

Feasibility experimental study on plugging leakage in goaf based on two-phase foam - Laisheng Huang; Bing Wu; Haiwei Cai; Chao Li; Jingxin Wang; Yang Li (Science of The Total Environment, 2024)

Derivation of water quality criteria for paraquat, bisphenol A and carbamazepine using quantitative structure-activity relationship and species sensitivity distribution (QSAR-SSD) - Ya-Qian Xu; Peng Huang; Xiang-Wei Li; Shu-Shen Liu; Bing-Qing Lu (Science of The Total Environment, 2024)

Joint effects of air pollution and genetic susceptibility on incident primary open-angle glaucoma - Hao-Neng Huang; Pan-Pan Zhu; Zhou Yang; Yi-Ming Tao; Xiaofeng Ma; Hai-Bing Yu; Li Li; Chun-Quan Ou (Science of The Total Environment, 2024)

Roof greening in major Chinese cities possibly afford a large potential carbon sink - Chao Yang; Yinghui Zhang; Min Chen; Song Zhu; Yuzhi Tang; Zhixin Zhang; Wei Ma; Huizeng Liu; Junyi Chen; Bohui Tang; Dejin Zhang; Zhengdong Huang; et al. (Science Bulletin, 2024)

Carbon-intercalated halloysite-based aerogel efficiently encapsulating phase change materials with excellent photothermal conversion and energy storage - Zongrui Zhang; Shiyu Huang; Pengxiao Wei; Shuangqing Li; Yafei Zhao; Yinze Yang; Bing Zhang (Chemical Engineering Journal, 2024)

Majorizing structural design and unraveling synergistic mechanisms in sulfide electrolytes via cationic and anionic modulation - Yaru Shi; Zheng Zhang; Qiuhong Li; Yiwen Sun; Jinlong Jiang; Bing Zhao; Shoushuang Huang; Yi Xu; Xueliang Sun; Jiujun Zhang; Yong Jiang (Chemical Engineering Journal, 2024)

A wearable electrochemical sensor for the monitoring of neonicotinoid insecticides, salicylic acid and the pH in plant guttation - Guanglei Chu; Siping Yu; Yuhang Wang; Weifeng Zhang; Bing Xue; Jinqi Huang; Zhiwei Wang; Jianghe Luo; Xia Sun; Ming Li (Chemical Engineering Journal, 2024)

Application of gauge-radar-satellite data in surface precipitation quality control - Shiying Li; Xiaolong Huang; Bing Du; Wei Wu; Yuhe Jiang (Meteorology and Atmospheric Physics, 2024)

Short-term exposure to ambient fine particulate matter constituents and myocardial infarction mortality - Yingxin Li; Bing Lu; Jing Wei; Qingqing Wang; Wancheng Ma; Rui Wang; Ruijun Xu; Zihua Zhong; Lu Luo; Xi Chen; Ziquan Lv; Suli Huang; et al. (Chemosphere, 2024)

Phosphorus recovery and tetracycline Mitigation: The role of Bacillus cereus LB-9 in struvite biomineralization from wastewater - Yi Meng; Muhammad Tajammal Munir; Xiaofeng Wu; Yuefei Huang; Wei Yu; Bing Li (Chemosphere, 2024)

Urban mangroves at risk: Understanding organophosphate flame retardant pollution at different urban function zones in shenzhen - Wenjun Zhao; Bing Li; Ruili Li; Xiaofeng Wu; Guanghui Lin; Yuefei Huang (Ocean & Coastal Management, 2024)

SIZ1-mediated SUMOylation of CPSF100 promotes plant thermomorphogenesis by controlling alternative polyadenylation - Zhibo Yu; Jun Wang; Cheng Zhang; Qiuna Zhan; Leqian Shi; Bing Song; Danlu Han; Jieming Jiang; Junwen Huang; Xiaolin Ou; Zhonghui Zhang; Jianbin Lai; et al. (Molecular Plant, 2024)

Electro-nitrification coupled with biological denitrification achieves efficient nitrogen removal from rare earth mine ammonia-nitrate wastewater - Qiming Li; Luanqi Zhou; Bing Li; Jing Liu; Shan Huang; Chenglong Zou; Zhanmeng Liu; Meng Zhang; Huimin Zhang (Journal of Water Process Engineering, 2024)

Deciphering the interplay between wastewater compositions and oxytetracycline in recovered struvite: Unveiling mechanisms and introducing control strategies - Degui Gao; Xiaofeng Wu; Yuefei Huang; Shungui Zhou; Guangqian Wang; Bing Li (Journal of Hazardous Materials, 2024)

Salinity responsive mechanisms of sulfur-based mixotrophic denitrification and ectoine induced tolerance enhancement - Ran Li; Ya-Nan Hou; Haibo Li; Yi Han; Daohong Zhang; Yuanyuan Song; Cong Huang; Jianbo Guo; Zhihua Liu; Wei Wei; Bing-Jie Ni (Chemical Engineering Journal, 2024)

Protective effects of docosahexaenoic acid supplementation on cognitive dysfunction and hippocampal synaptic plasticity impairment induced by early postnatal PM2.5 exposure in young rats - Jianxiong Gui; Mingdan Xie; Lingman Wang; Bing Tian; Benke Liu; Hengsheng Chen; Li Cheng; Dishu Huang; Ziyao Han; Xiaoyue Yang; Jie Liu; Li Jiang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Plasma Deoxycholic Acid Levels are Associated with Hemodynamic and Clinical Outcomes in Acute Pulmonary Embolism Patients - Na Sun; Yi-Qiang Chen; Yan-Sheng Chen; Lei Gao; Run-Wei Deng; Jing Huang; You-Li Fan; Xuan Gao; Bin-Feng Sun; Na-Na Dong; Bo Yu; Xia Gu; et al. (Cardiovascular Toxicology, 2024)

Extremely 26Mg-enriched authigenic clays from the Ediacaran Doushantuo Formation (South China) indicating the coupled carbonate-silicate diagenesis - Tianzheng Huang; Bing Shen; Xiaoli Wang; Haoran Ma; Chao Li; Chuanming Zhou (Global and Planetary Change, 2024)

Polygonatum kingianum Coll. et Hemsl enzymatic saccharifying extracts alleviate HFD-induced obesity in mice via regulating gut microbiota and AMPK pathways - Yanli Li; Junyuan Huang; Wenjun Zhao; Ziwen Guan; Ziyu Wang; Hong Huang; Rongxiang Guo; Lei Zhao; Pan Li; Bing Du (Food Bioscience, 2024)

Long-term reduced and no tillage increase maize (Zea mays L.) grain yield and yield stability in Northeast China - Yan-Jie Lv; Xiao-Long Zhang; Lei Gong; Shou-Bing Huang; Bao-Long Sun; Jin-Yu Zheng; Yong-Jun Wang; Li-Chun Wang (European Journal of Agronomy, 2024)

Struvite biomineralization as a promising solution to break the pollutant-resource paradox of phosphorus - Baorui Liang; Degui Gao; Muhammad Tajammal Munir; Wei Yu; Xiaofeng Wu; Yuefei Huang; Han Li; Brent Young; Shungui Zhou; Bing Li (Chemical Engineering Journal, 2024)

Mutually reinforced cancer treatment based on phototherapy combined with ferroptosis - Guan-Hong Chen; Lei Gan; Li-Yuan Tian; Bin-Xin Huang; Qiang Xiao; Yi-Jing Zhang; Mei-Tian Xiao; Bing-De Zheng; Jing Ye (Chemical Engineering Journal, 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

The urgent need to reduce phosphorus discharges for sustainable mangrove wetland management - Lixia Qiu; Enhao Wang; Ruili Li; Xiaofeng Wu; Yuefei Huang; Guanghui Lin; Bing Li (Water Research, 2024)

Spatial distribution and assembly processes of bacterial communities in riverine and coastal ecosystems of a rapidly urbanizing megacity in China - Hebin Liang; Jin Huang; Yu Xia; Ying Yang; Yang Yu; Kai Zhou; Lin Lin; Xiaoyan Li; Bing Li (Science of The Total Environment, 2024)

Transcriptomic and metabolomic insights into the antimony stress response of tall fescue (Festuca arundinacea) - Jibiao Fan; Yao Chen; Xiaoqin Li; Jianbo Huang; Xingyu Zhang; Ke Chen; Yuanhang Xiang; Fangming Wu; Xuebing Yan; Bing Wen (Science of The Total Environment, 2024)

Non-transcriptional regulatory activity of SMAX1 and SMXL2 mediates karrikin-regulated seedling response to red light in Arabidopsis - Wenwen Chang; Qiao Qiao; Qingtian Li; Xin Li; Yanyan Li; Xiahe Huang; Yingchun Wang; Jiayang Li; Bing Wang; Lei Wang (Molecular Plant, 2024)

STIM1 mediates methamphetamine-induced neuronal autophagy and apoptosis - Qin Tian; Jie Zhou; Zhenzhen Xu; Bin Wang; Jiashun Liao; Ke Duan; Xiaoting Li; Enping Huang; Wei-Bing Xie (NeuroToxicology, 2024)

Potential structure–function relationships of pectic polysaccharides from quinoa microgreens: Impact of various esterification degrees - Jie Li; Jing Feng; Xiao Luo; Mei-Mei Qu Mo; Wen-Bing Li; Jing-Wei Huang; Shengpeng Wang; Yi-Chen Hu; Liang Zou; Ding-Tao Wu (Food Research International, 2024)

Experimental study on pulsed pneumatic pre-fracturing grouting in sandy and clayey-silty hydrate-bearing sediments - Shuhan Lai; Feng Huang; Kun Chen; Yanchao Liu; Bing Li; Fang Jin; Guobiao Zhang; Yun Qi (Gas Science and Engineering, 2024)

Exploration of the immune response of grass carp (Ctenopharyngodon idellus) erythrocytes during bacterial infection - Shiyi Yang; Yanhan Bai; Junjie Tao; Chengming Tu; Bing Chen; Xiaoman Huang; Linpeng Zhang; Lihan Liu; Lin Li; Zhendong Qin (Fish & Shellfish Immunology, 2024)

Near-infrared laser induced direct ignition of 4,4′,5,5′-tetranitro-1H,1′H-[2,2′-biimidazole]-1,1′-diamine by constructing diverse crystal structures - Ping Ye; Weimiao Wang; Xiaodong Li; Zhiqiang Qiao; Yirui Lu; Bing Huang; Liangfei Bai; Liang Chen; Xiaoqing Tu; Rui Li; Guangcheng Yang; Guoqing Lv (Chemical Engineering Journal, 2024)

A neural m6A pathway regulates behavioral aggregation in migratory locusts - Xianliang Huang; Qing Li; Yanan Xu; Ang Li; Shanzheng Wang; Yusheng Chen; Chunrui Zhang; Xia Zhang; Hailin Wang; Cong Lv; Baofa Sun; Shaoqin Li; et al. (Science China Life Sciences, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Resveratrol ameliorates DSS-induced ulcerative colitis by acting on mouse gut microbiota - Bing Yu; Ying Wang; Zekai Tan; Zhengyi Hong; Lewen Yao; Shiyuan Huang; Zexi Li; Lanyue Zhang; Hui Li (Inflammopharmacology, 2024)

Exogenous carbon addition soil mediated phosphorus dynamics under eight years continuous input of swine manure in a wheat-rice rotation - Chunlong Zhang; Xiaoyan Tang; Changquang Wang; Edith le Cadre; Rong Huang; Qi Tao; Yingjie Wu; Youlin Luo; Qiang Xu; Genchuan Bai; Bing Li (Agriculture, Ecosystems & Environment, 2024)

A literature review on phosphate removal from wastewater by lanthanum-based adsorbents: From mechanisms to applications - Yao-Yao Lu; Hao Wang; Rong-Rong Chang; Wen-Bing Li; Bao-Cheng Huang; Ren-Cun Jin (Journal of Water Process Engineering, 2024)

Biotransformation of HBCDs by the microbial communities enriched from mangrove sediments - Fei Yu; Bing Zhang; Yongjin Liu; Wenqi Luo; Haonan Chen; Jun’na Gao; Xueying Ye; Jin Li; Qingyi Xie; Tao Peng; Hui Wang; Tongwang Huang; et al. (Journal of Hazardous Materials, 2024)

Development and validation of a liquid chromatography tandem mass spectrometry method for the determination of 10 mycotoxins in beer of the Chinese market and exposure estimate - Tianyang Wu; Kun Kang; Ying Xia; Huan Deng; Bing Han; Xiaoyu Han; Yiding Xie; Chenyu Li; Jicheng Zhan; Weidong Huang; Yilin You (Food Research International, 2024)

Unravelling the safety improving and failure mechanisms of a 56.5 Ah high-energy–density Li-ion cell containing solid-state electrolyte - Wei Zhang; Xiaopeng Qi; Min Liu; Bingxue Liu; Yuansen Hu; Jing Ye; Rennian Wang; Bin Li; Changhong Wang; Qian Huang; Bing Yu; Rong Yang; et al. (Chemical Engineering Journal, 2024)

Investigation on Mechanical and Failure Characteristics of Sandstone with Flaw - Zheng-Hua Gao; Qing Li; Chen Huang; Tong-De Zhao; Bing-Bing Yu; Shao-Kun Liu (Geotechnical and Geological Engineering, 2024)

Pseudocercones A-C, three new polyketide derivatives from the endophytic fungus Pseudocercospora sp. TSS-1 - Wei-Wei Peng; Min Kuang; Yuan-Tao Huang; Mei-Fang Li; Yu-Ting Zheng; Li Xu; Jian-Bing Tan; Feng-Hua Kang; Hai-Bo Tan; Zhen-Xing Zou (Natural Product Research, 2024)

Immune response mechanisms underlying bacterial infection in Aquarana catesbeiana erythrocytes - Yanhan Bai; Lingqin Lu; Junjie Tao; Chengming Tu; Bing Chen; Shiyi Yang; Xiaoman Huang; Linpeng Zhang; Lihan Liu; Li Lin; Zhendong Qin (Aquaculture, 2024)

Dietary short-term supplementation of grape seed proanthocyanidin extract improves pork quality and promotes skeletal muscle fiber type conversion in finishing pigs - Yiqiang Li; Yadi Feng; Xiaoling Chen; Jun He; Yuheng Luo; Bing Yu; Daiwen Chen; Zhiqing Huang (Meat Science, 2024)

Degradation of prometryn during UV/persulfate process: Kinetics and disinfection by-product formation - Chen-Yan Hu; Hao Liu; Ling Xu; Yi-Li Lin; Qiang-Bing Wang; Dan-Dan Huang; Yi-Hui Wu; Zi-Yi Dong; Sheng-Jie Ji (Journal of Water Process Engineering, 2024)

Efficient removal of ammonia nitrogen via a coupled system of Ni1Cu0.2-Se-T/CP anode and copper foam cathode - Luanqi Zhou; Bing Li; Hailong Wang; Qiming Li; Shan Huang; Dingchang Li; Sulin Xiang; Meng Zhang; Huimin Zhang (Journal of Environmental Chemical Engineering, 2024)

Experimental investigation of microscale mechanical alterations in shale induced by fracturing fluid contact - Hai Huang; Wentong Zhang; Huaqiang Shi; Jun Ni; Li Ding; Bing Yang; Yong Zheng; Xinru Li (Gas Science and Engineering, 2024)

Non-destructively incorporating ceria in Nafion membrane as hydroxyl radical scavenging agent for long-term PEMFC application - Guodong Xu; Anqi Ke; Feng Ji; Yuxin Liu; Zhiyuan Zhao; Rongguan Lv; Bing Huang; Jing Li; Chengwei Deng; Yuzhen Sun; Weiwei Cai (Fuel, 2024)

Effects of glycerol and PVA on gelatin/Gum Arabic aerogels: Microstructure, mechanical properties, and applications for food monitoring - Binghang Li; Miaomiao Chen; Yuan Wu; Bing Liu; Gangliang Huang (Food Hydrocolloids, 2024)

PCSK9 regulates myocardial ischemia–reperfusion injury through parkin/pink1-mediated autophagy pathway - Guangwei Huang; Hailong Bao; Peng Zhan; Xiyang Lu; Zonggang Duan; Xinlin Xiong; Muzhi Lin; Bing Wang; Hongxin An; Luanda Xiahou; Haiyan Zhou; Zhenhua Luo; et al. (Molecular & Cellular Toxicology, 2024)

Effects of New Psychoactive Substance Esketamine on Behaviors and Transcription of Genes in Dopamine and GABA Pathways in Zebrafish Larvae - Si-Ying Li; Wen-Jun Shi; Dong-Dong Ma; Jin-Ge Zhang; Zhi-Jie Lu; Xiao-Bing Long; Xin Liu; Chu-Shu Huang; Guang-Guo Ying (Bulletin of Environmental Contamination and Toxicology, 2024)

Flexible microfluidic colorimetric detection chip integrated with ABTS·+ and Co@MnO2 nanozyme catalyzed TMB reaction systems for bio-enzyme free detection of sweat uric acid - Fang Li; Jianming Jiang; Nuotong Shen; Hao Peng; Yi Luo; Nannan Li; Liyang Huang; Yuyang Lu; Lifu Liu; Bing Li; Jianbo He (Analytica Chimica Acta, 2024)

Outdoor artificial light at night and incident cardiovascular disease in adults: A national cohort study across China - Xiangming Hu; Le-Bing Wang; Bin Jalaludin; Luke D. Knibbs; Steve Hung Lam Yim; Xiang Qian Lao; Lidia Morawska; Zhiqiang Nie; Yingling Zhou; Li-Wen Hu; Wen-Zhong Huang; Yanqiu Ou; et al. (Science of The Total Environment, 2024)

Effects of farmland residual mulch film-derived microplastics on the structure and function of soil and earthworm Metaphire guillelmi gut microbiota - Huimei Tian; Chuanwei Zheng; Xinjie Huang; Chen Qi; Bing Li; Zhongkun Du; Lusheng Zhu; Jinhua Wang; Jun Wang (Science of The Total Environment, 2024)

Identification candidate genes for salt resistance through quantitative trait loci-sequencing in Brassica napus L. - Yan Zhang; Zhiting Guo; Xiaoqin Chen; Xinru Li; Yiji Shi; Liang Xu; Chengyu Yu; Bing Jing; Weiwei Li; Aixia Xu; Xue Shi; Keqi Li; et al. (Journal of Plant Physiology, 2024)

Integrated morphological, physiological and transcriptomic analyses reveal response mechanisms of rice under different cadmium exposure routes - Qin Dong; Yingjie Wu; Haidong Wang; Bing Li; Rong Huang; Huanxiu Li; Qi Tao; Qiquan Li; Xiaoyan Tang; Qiang Xu; Youlin Luo; Changquan Wang (Journal of Hazardous Materials, 2024)

Investigating the antibiotic resistance genes and their potential risks in the megacity water environment: A case study of Shenzhen Bay Basin, China - Hebin Liang; Jin Huang; Yi Tao; Uli Klümper; Thomas U. Berendonk; Kai Zhou; Yu Xia; Ying Yang; Yang Yu; Ke Yu; Lin Lin; Xiaoyan Li; et al. (Journal of Hazardous Materials, 2024)

A molecular imprinting photoelectrochemical sensor modified by polymer brushes and its detection for BSA - Xin Li; Bing Li; Jie Huang; Haiyan Zhu; Ying Li; Gang Shi (Chemical Engineering Journal, 2024)

A four-band index for both liquid and solid water and its applications in the Aral Sea Basin - Bing Yue; Xi Chen; Saibo Li; Zhengping Du; John Wilson; Junhui Yang; Yimen Jiao; Shuangyan Huang; Chenghu Zhou (Science China Earth Sciences, 2024)

Dietary ellagic acid supplementation improves meat quality in growing-finishing pigs - Tengteng Huang; Huawei Li; Xiaoling Chen; Daiwen Chen; Jun He; Bing Yu; Yuheng Luo; Ping Zheng; Hong Chen; Zhiqing Huang (Animal Feed Science and Technology, 2024)

A system dynamics simulation-based strategic analysis of integrated water resources utilization and management in Shenzhen city - Guangzhi Zheng; Jing-Cheng Han; Ping Li; Bing Li; Xiaofeng Wu; Yuefei Huang; Muhammad Ahmad (Environmental Science and Pollution Research, 2024)

Mechanistic insights into the effects of diuron exposure on Alexandrium pacificum - Dan Huang; Cai-Qin Cheng; Jiang-Bing Qiu; Yun Huang; Hao-Yun Zhang; Zhen-Hao Xu; Si-Wei Wu; Yi-Tong Huang; Jian Chen; Li-Gong Zou; Wei-Dong Yang; Xiao-Fei Zheng; et al. (Water Research, 2024)

Autophagy alleviates hippocampal neuroinflammation by inhibiting the NLRP3 inflammasome in a juvenile rat model exposed particulate matter - Jianxiong Gui; Jie Liu; Lingman Wang; Xiaoyue Yang; Bing Tian; Hanyu Luo; Dishu Huang; Ziyao Han; Jiaxin Yang; Ran Ding; Zhixu Fang; Xue Li; et al. (Toxicology, 2024)

A novel method of identifying estuary high-nutrient zones for water quality management - Linlin Wang; Xiaoyu Lei; Guo Yuehua; Yang Zhou; Jing-Cheng Han; Yuefei Huang; Bing Li; Xian-zhong Mao; Zhaozhao Tang (Science of The Total Environment, 2024)

Evidence for the transportation of aggregated microplastics in the symplast pathway of oilseed rape roots and their impact on plant growth - Sashuang Rong; Shutao Wang; Hongmei Liu; Yuxin Li; Jia Huang; Wanqing Wang; Bing Han; Shiming Su; Wei Liu (Science of The Total Environment, 2024)

Assessing the impact of water-sediment factors on water quality to guide river-connected lake water environment improvement - Mingming Geng; Zhan Qian; Heng Jiang; Bing Huang; Shuchun Huang; Bo Deng; Yi Peng; Yonghong Xie; Feng Li; Yeai Zou; Zhengmiao Deng; Jing Zeng (Science of The Total Environment, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Clerodane diterpenoids with in-vitro anti-neuroinflammatory activity from the tuberous root of Tinospora sagittata (Menispermaceae) - Jia-Qi Song; Kai-Cheng Yang; Xian-Zhe Fan; Li Deng; Yang-Li Zhu; Hong Zhou; Ya-Si Huang; Xiang-Qian Kong; Li-Jun Zhang; Hai-Bing Liao (Phytochemistry, 2024)

Adaptation and remediation strategies of mangroves against heavy metal contamination in global coastal ecosystems: A review - Shafeeq Ur Rahman; Jing-Cheng Han; Yang Zhou; Muhmmad Ahmad; Bing Li; Yuchen Wang; Yuefei Huang; Ghulam Yasin; Mohammad Javed Ansari; Mohd Saeed; Irfan Ahmad (Journal of Cleaner Production, 2024)

Composition of DOM along the depth gradients in the paddy field treated with crop straw for 10 years - Rong Huang; Zheng Li; Yi Xiao; Jiang Liu; Tao Jiang; Ouping Deng; Xiaoyang Tang; Yingjie Wu; Qi Tao; Qiquan Li; Youlin Luo; Xuesong Gao; et al. (Journal of Environmental Management, 2024)

The infection of Aeromonas hydrophila activated Multiple programmed cell death pathways in red blood cells of Clarias fuscus - Junjie Tao; Chengming Tu; Zizheng Xu; Yanhan Bai; Bing Chen; Shiyi Yang; Xiaoman Huang; Linpeng Zhang; Lihan Liu; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2024)

Revisiting the Mg isotopic systematics of siliciclastic components of sediments and sedimentary rocks: A new geochemical proxy of continental weathering in Earth’s history - Tianzheng Huang; Bing Shen; Kangjun Huang; Meng Ning; Chao Li; Jinzhuang Xue; Yuanlin Sun; Baoqi Huang (Science China Earth Sciences, 2024)

One-time root-zone fertilization of controlled-release urea increases nitrogen use efficiency while reducing nitrogen loss risk in a ratoon rice field under two irrigation practices - Zijuan Ding; Jintao Li; Fei Huang; Ren Hu; Shaobing Peng; Jianliang Huang; Jun Hou; Jianli Zhou; Chengfang Li; Bing Su; Mingjian Xu (Nutrient Cycling in Agroecosystems, 2024)

Ucp4 Knockdown of Cerebellar Purkinje Cells Induces Bradykinesia - Ya-Yun Wang; Hui Liu; Shu-Jiao Li; Ban Feng; Yun-Qiang Huang; Shui-Bing Liu; Yan-Ling Yang (Molecular Neurobiology, 2024)
Although uncoupling protein 4 (UCP4) is the most abundant protein reported in the brain, the biological function of UCP4 in cerebellum and pathological outcome of UCP4 deficiency in cerebellum remain obscure. To evaluate the role of Ucp4 in the cerebellar Purkinje cells (PCs), we generated the conditional knockdown of Ucp4 in PCs ( Pcp2 cre ;Ucp4 fl/fl mice) by breeding Ucp4 fl/fl mice with Pcp2 cre mice. Series results by Western blot, immunofluorescent staining, and triple RNAscope in situ hybridization confirmed the specific ablation of Ucp4 in PCs in Pcp2 cre ;Ucp4 fl/fl mice, but did not affect the expression of Ucp2 , the analog of Ucp4 . Combined behavioral tests showed that Pcp2 cre ;Ucp4 fl/fl mice displayed a characteristic bradykinesia in the spontaneous movements. The electromyogram recordings detection excluded the possibility of hypotonia in Pcp2 cre ;Ucp4 fl/fl mice. And the electrical patch clamp recordings showed the altered properties of PCs in Pcp2 cre ;Ucp4 fl/fl mice. Moreover, transmission electron microscope (TEM) results showed the increased mitochondrial circularity in PCs; ROS probe imaging showed the increased ROS generation in molecular layer; and finally, microplate reader assay showed the significant changes of mitochondrial functions, including ROS, ATP, and MMP in the isolated cerebellum tissue. The results suggested that the specific knockdown of mitochondrial protein Ucp4 could damage PCs possibly by attacking their mitochondrial function. The present study is the first to report a close relationship between UCP4 deletion with PCs impairment, and suggests the importance of UCP4 in the substantial support of mitochondrial function homeostasis in bradykinesia. UCP4 might be a therapeutic target for the cerebellar-related movement disorder. Graphical Abstract

Anthropogenic disturbance driving population decline of a dominant tree in East Asia evergreen broadleaved forests over the last 11,000 years - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Shuang‐Xiu Xu; Jie Liu; Feng‐Mao Yang; Ya‐Huang Luo; Jun‐Wei Ye; Yao Zhao; Jun Rong; Bing Liu; Peng‐Fei Ma; De‐Zhu Li (Conservation Biology, 2024)
Current biodiversity loss is generally considered to have been caused by anthropogenic disturbance, but it is unclear when anthropogenic activities began to affect biodiversity loss. One hypothesis suggests it began with the Industrial Revolution, whereas others propose that anthropogenic disturbance has been associated with biodiversity decline since the early Holocene. To test these hypotheses, we examined the unique vegetation of evergreen broadleaved forests (EBLFs) in East Asia, where humans have affected landscapes since the early Holocene. We adopted a genomic approach to infer the demographic history of a dominant tree ( Litsea elongata ) of EBLFs. We used Holocene temperature and anthropogenic disturbance factors to calculate the correlation between these variables and the historical effective population size of L. elongata with Spearman statistics and integrated the maximum‐entropy niche model to determine the impact of climate change and anthropogenic disturbance on fluctuation in its effective population size. We identified 9 well‐defined geographic clades for the populations of L. elongata . Based on the estimated historical population sizes of these clades, all the populations contracted, indicating persistent population decline over the last 11,000 years. Demographic history of L . elongata and human population change, change in cropland use, and change in irrigated rice area were significantly negatively correlated, whereas climate change in the Holocene was not correlated with demographic history. Our results support the early human impact hypothesis and provide comprehensive evidence that early anthropogenic disturbance may contribute to the current biodiversity crisis in East Asia.

Removal and recovery of phosphate by modified oyster shell and its fertilizer application - Ping Li; Jianxu Li; Weirui Chen; Xiujuan Guan; Bing Tang; Liying Bin; Shaosong Huang (Science of The Total Environment, 2024)

Adaptive evolution in asymptomatic host confers MDR Salmonella with enhanced environmental persistence and virulence - Bing He; Ting-ting Zhu; Yin Liang; Hai-jing Wei; Zi-lei Huang; Li-jie Liang; Jia-hao Zhong; Yang Luo; Xin-lei Lian; Dong-hao Zhao; Xiao-ping Liao; Ya-hong Liu; et al. (Science of The Total Environment, 2024)

Climate warming enhances chemical weathering in permafrost-dominated eastern Siberia - Ping Wang; Qiwei Huang; Shiqi Liu; Yu Liu; Zehong Li; Sergey P. Pozdniakov; Tianye Wang; Ekaterina S. Kazak; Natalia L. Frolova; Olga I. Gabysheva; Jialing Zhang; Bing Bai; et al. (Science of The Total Environment, 2024)

HaMYBA-HabHLH1 regulatory complex and HaMYBF fine-tune red flower coloration in the corolla of sunflower (Helianthus annuus L.) - Wenhui Jiang; Qinqin Jiang; Zhijie Shui; Peipei An; Shandang Shi; Tianxiang Liu; Hanbing Zhang; Shuyi Huang; Bing Jing; Enshi Xiao; Li Quan; Jixia Liu; et al. (Plant Science, 2024)

Back-reef and lagoonal communities, Givetian (Middle Devonian) in Guangdong, South China: Their role in global Devonian reef development - Yang Tian; Lingzhan Wang; Bing Tu; Guogang Xie; Jiayuan Huang; Stephen Kershaw; Kun Liang; Yue Li; Wenkun Qie (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Abating ammonia emission from poultry manure by Pt/TiO2 modified corn straw - Yunhong Jiao; Jie Huang; Jing Hu; Anthony J. Weatherley; Wei Liu; Chaoyu Li; Zhiling Ma; Bing Han (Journal of Environmental Management, 2024)

Combined metabolome and transcriptome analysis reveals a critical role of lignin biosynthesis and lignification in stem-like pneumatophore development of the mangrove Avicennia marina - Yu-Chen Zhang; Li-Han Zhuang; Jia-Jie Zhou; Shi-Wei Song; Jing Li; He-Zi Huang; Bing-Jie Chi; You-Hui Zhong; Jing-Wen Liu; Hai-Lei Zheng; Xue-Yi Zhu (Planta, 2024)

The influence of Acetobacter pomorum bacteria on the developmental progression of Drosophila suzukii via gluconic acid secretion - Xiao‐Li Bing; Zi‐Jian Liang; Jia Tian; Xue Gong; Shao‐Qiu Huang; Jie Chen; Xiao‐Yue Hong (Molecular Ecology, 2024)
Insects are rich in various microorganisms, which play diverse roles in affecting host biology. Although most Drosophila species prefer rotten fruits, the agricultural pest Drosophila suzukii attacks ripening fruits before they are harvested. We have reported that the microbiota has positive and negative impacts on the agricultural pest D. suzukii on nutrient‐poor and ‐rich diets, respectively. On nutrient‐poor diets, microbes provide protein to facilitate larval development. But how they impede D. suzukii development on nutrient‐rich diets is unknown. Here we report that Acetobacter pomorum (Apo), a commensal bacterium in many Drosophila species and rotting fruit, has several detrimental effects in D. suzukii . Feeding D. suzukii larvae nutrient‐rich diets containing live Apo significantly delayed larval development and reduced the body weight of emerged adults. Apo induced larval immune responses and downregulated genes of digestion and juvenile hormone metabolism. Knockdown of these genes in germ‐free larvae reproduced Apo‐like weakened phenotypes. Apo was confirmed to secrete substantial amounts of gluconic acid. Adding gluconic acid to the D. suzukii larval diet hindered larval growth and decreased adult body weight. Moreover, the dose of gluconic acid that adversely affected D. suzukii did not negatively affect Drosophila melanogaster , suggesting that D. suzukii is less tolerant to acid than D. melanogaster . Taken together, these findings indicate that D. suzukii is negatively affected by gluconic acid, which may explain why it prefers ripening fruit over Apo‐rich rotting fruit. These results show an insect's tolerance to microbes can influence its ecological niche.

Toxic effects of lead (Pb), cadmium (Cd) and tetracycline (TC) on the growth and development of Triticum aestivum: A meta-analysis - Shafeeq Ur Rahman; Jing-Cheng Han; Muhammad Ahmad; Shuai Gao; Khalid Ali Khan; Bing Li; Yang Zhou; Xu Zhao; Yuefei Huang (Science of The Total Environment, 2023)

Study on the impact of the perforated floating breakwater on coastal bridge with box-girder superstructure under two-dimensional focused waves - Lin Li; Bo Huang; Shuhang Qian; Zhiying Yang; Jianting Zhou; Qingyang Ren; Bing Zhu (Ocean Engineering, 2023)

Separatable polydopamine-coated cobalt-chitosan beads for Cr(VI) removal from wastewater with superior capacity - Yimin Huang; Xueyan Li; Yan Peng; Hua Zhang; Anxian Shi; Xiujun Deng; Baoling Wang; Yingtang Zhou; Bing Wang; Guangzhi Hu (Journal of Environmental Chemical Engineering, 2023)

Ephedrine and cocaine cause developmental neurotoxicity and abnormal behavior in zebrafish - Dong-Dong Ma; Wen-Jun Shi; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Xiao-Bing Long; Xin Liu; Chu-Shu Huang; Guang-Guo Ying (Aquatic Toxicology, 2023)

Highly specific detection of Neisseria gonorrhoeae based on recombinase polymerase amplification-initiated strand displacement amplification - Mengnan Fan; Jianru Yang; Xiaosu Wang; Yongjie Xu; Bing Li; Hui Yang; Qin Lu; Xun Min; Meirong Huang; Jian Huang (Analytica Chimica Acta, 2023)

Overcoming the fluorescent interference during Raman spectroscopy detection of microplastics - Yu Liu; Jiale Hu; Liqian Lin; Bing Yang; Minhua Huang; Min Chang; Xiaoxin Huang; Zhenqing Dai; Shengli Sun; Lei Ren; Chengyong Li (Science of The Total Environment, 2023)

The effect of flow rate on the ammonia oxidation rate in the riverway biofilm in-situ remediation and modeling - Bing Liu; Gaoyuan Geng; Peiliang Xie; Yuying Huang; Feiyong Chen; Jing Wang; Yuxi Chen; Hidenari Yasui; Quanyong Wang; Rajeev Goel; Yifan Li (Process Safety and Environmental Protection, 2023)

Machine learning–based optimal design of the in-situ leaching process parameter (ISLPP) for the acid in-situ leaching of uranium - Bing Wang; Yue Luo; Jia-zhong Qian; Jin-hui Liu; Xun Li; Yan-hong Zhang; Qian-qian Chen; Li-yao Li; Da-ye Liang; Jian Huang (Journal of Hydrology, 2023)

Trithiocyanurate-functionalized hydrochar for effectively removing methylene blue and Pb (II) cationic pollutants - Shen-Ao Huang; Hua-Jing Teng; Yin-Tao Su; Xiao-Meng Liu; Bing Li (Environmental Pollution, 2023)

Sources of antimony contamination and its migration into water systems of Xikuangshan, China: Evidence from hydrogeochemical and stable isotope (H, O, S, and Sr) signatures - Bing Wen; Aiguo Zhou; Jianwei Zhou; Jianbo Huang; Tao Long; Xiaocen Jia; Weiqing Zhou; Wanyu Li (Environmental Pollution, 2023)

Advancing sustainable phosphorus removal and recovery with Metal-Organic frameworks (MOFs) - Degui Gao; Haodong Ji; Ruili Li; Muhammad Tajammal Munir; Xiaofeng Wu; Yuefei Huang; Bing Li (Chemical Engineering Journal, 2023)

Fundicoccus culcitae sp. nov., a novel potential bacteriocin producing bacterium isolated from a spoiled eye mask - Gang Zhou; Lei Gao; Bao-Zhu Fang; Ying-Si Wang; Hong-Bing Tao; Xia Wen; Qian Wang; Xiao-Mo Huang; Qing-Shan Shi; Wen-Jun Li; Xiao-Bao Xie (Antonie van Leeuwenhoek, 2023)

Genome-centric metagenomics provides new insights into metabolic pathways of polyhydroxyalkanoates biosynthesis and functional microorganisms subsisting on municipal organic wastes - Ruo-hong Li; Jin Huang; Cheng-xi Liu; Ke Yu; Feng Guo; You Li; Zuo-hong Chen; Xuan Wang; Ren-xin Zhao; Jia-yu Zhang; Jia-jin Liang; Yun Li; et al. (Water Research, 2023)

Numerical study on the behaviors of coastal bridges with box girder under the action of extreme waves - Zhiying Yang; Bing Zhu; Bo Huang; Jie Hou; Yuezhi Zhang; Lin Li (Ocean Engineering, 2023)

Inhibition mechanism of chlorobenzene on NH3-SCR side reactions over MnOx-CeO2 confined titania nanotubes - Yifan Li; Yaqin Hou; Biao Li; Yatao Yang; Shuang Ma; Bing Wang; Guozhen Qin; Zhanggen Huang (Fuel, 2023)

Contrasting effects of rice husk and its biochar on N2O emissions and nitrogen leaching from Lei bamboo soils under subtropical conditions - Rong Zhou; Zhe Chen; Ali EI-Naggar; Linlin Tian; Chengpeng Huang; Zhen Zhang; Kumuduni Niroshika Palansooriya; Yongfu Li; Bing Yu; Scott X. Chang; Yanjiang Cai (Biology and Fertility of Soils, 2023)

Effects of Snail Bellamya purificata Farming at Different Stocking Densities on the Algal and Fungal Communities in Sediment - Yiran Hou; Mengmeng Zhou; Rui Jia; Wei Sun; Yanhong Yang; Xiongjian Huang; Bing Li; Jian Zhu (Fishes, 2023)
The snail Bellamya purificata is recognized as a potential bio-remediation species, and is commonly employed in polyculture to enhance resource utilization efficiency and realize culture environment regulation. In order to enrich the microbiome studies on elucidating the ecological effects of snail B. purificata farming, we assessed the effect of B. purificata farming activities, at varying stocking densities, on the algal and fungal communities in sediment. Four experimental groups were established in our study, each corresponding to a different stocking density: 0, 234.38, 468.75, and 937.5 g/m2, represented as CON, LD, MD, and HD, respectively. High-throughput sequencing based on ITS and 23S ribosomal RNA (rRNA) genes was employed to analyze the variations in algal and fungal communities under B. purificata farming activities at different stocking densities. B. purificata farming activities had no significant effect on the alpha diversities of fungal and algal communities, but significantly altered the compositions of fungal and algal communities in sediments, especially B. purificata farming activity at low stocking density. B. purificata farming activities at low stocking density could significantly increase the relative abundances of fungal genera Paraconiothyrium and Penicillium compared with the CON group. The promoting effect diminished with increasing density. B. purificata farming activities at low or medium stocking density also could enhance the relative abundances of algal genera Microchloropsis, Scenedesmus, and Auxenochlorella. Hence, B. purificata farming activity at low stocking density might be the optimum density to enhance resource utilization efficiency and minimize environmental pollution.

Description of a natural infection with decapod iridescent virus 1 in farmed swimming crab - Liang Qiu; Xiao-Meng Guo; Guo-Si Xie; Yong-Hui Feng; Jing-Yi Xing; Chen Li; Bing Yang; Jie Huang (Aquaculture, 2023)

Insights into the life-cycle of aerobic granular sludge in a continuous flow membrane bioreactor by tracing its heterogeneous properties at different stages - Biao Yang; Weifeng Liang; Liying Bin; Weirui Chen; Xinyi Chen; Ping Li; Shanglong Wen; Shaosong Huang; Bing Tang (Water Research, 2023)

Heterogeneous mantle source compositions for boninite from Bonin and Troodos, evidence from iron isotope variations - Yuanyuan Xiao; Yongxiang Yao; Zihang Huang; Yi-Bing Li; Yaoling Niu; Teruaki Ishii; Ziwei Sun; Hongmei Gong; Xiaohong Wang (Lithos, 2023)

Multiple insights into lignin-mediated cadmium detoxification in rice (Oryza sativa) - Qin Dong; Yingjie Wu; Bing Li; Xi Chen; Lu Peng; Zulfiqar Ali Sahito; Huanxiu Li; Yulan Chen; Qi Tao; Qiang Xu; Rong Huang; Youlin Luo; et al. (Journal of Hazardous Materials, 2023)

Simultaneous removal of microplastics and doxycycline and preparation of novel hollow carbon nanocakes by pyrolysis - Yuzhi Liu; Bing Li; Ruili Li; Haodong Ji; Lan Song; Xiaoshan Zhu; Lu Jing; Xiaoning Liu; Yuefei Huang; Xiaofeng Wu (Chemical Engineering Journal, 2023)

Nanocomposite scintillation perovskite-delignified wood photonic guides for X-ray imaging - Yifan Zhou; Zhiliang Deng; Bing Wang; Pei Li; Lingxi Li; Wenmin Han; Jie Huang; Wenbao Jia; Xiaoping Ouyang; Qiang Xu; Kostya (Ken) Ostrikov (Chemical Engineering Journal, 2023)

Punicalagin alleviates the hyperproliferation of keratinocytes in psoriasis through inhibiting SKP2 expression - Lipeng Tang; Bowen Zhang; Guanzhuo Li; Ying Zhu; Bing Feng; Zuqing Su; Wenhui Han; Huilin Huang; Qiuping Li; Maojie Wang; Yuchao Chen; Huazhen Liu; et al. (Journal of Natural Medicines, 2023)

High fat diet induces brain injury and neuronal apoptosis via down-regulating 3-β hydroxycholesterol 24 reductase (DHCR24) - Ziyin Lu; Haozhen Wang; Xiujin Zhang; Xiuting Huang; Shan Jiang; Yang Li; Ting Liu; Xiuli Lu; Bing Gao (Cell and Tissue Research, 2023)

Geochemical behaviors of uranium and thorium during weathering and pedogenesis of carbonate rock: constraint from their speciation - Qiang Ma; Bing-jie Zhou; Zhi-gang Feng; Xiao-long Wang; Rong Chen; Pei-shan Li; Chong Huang (Environmental Science and Pollution Research, 2023)

MiR-425-5p suppression of Crebzf regulates oocyte aging via chromatin modification - Kadiliya Jueraitetibaike; Ting Tang; Rujun Ma; Shanmeizi Zhao; Ronghua Wu; Yang Yang; Xuan Huang; Xi Cheng; Cheng Zhou; Hong Zhang; Lu Zheng; Xie Ge; et al. (GeroScience, 2023)
Female infertility due to declining oocyte quality with age remains a significant challenge for patients and physicians, despite extensive research efforts. Recent studies suggest that microRNAs (miRNAs), which respond to various stressors in the aging process, may provide a promising solution. With the approval of small RNA drugs for clinical use, miRNA-based treatment of oocyte aging appears to be a viable option. Through high-throughput sequencing, miR-425-5p was identified as the only miRNA elevated under natural aging and oxidative stress. Microinjection of inhibitors to inhibit miR-425-5p effectively improved compromised phenotypes of old oocytes in vitro. Further investigation revealed that Crebzf acts as a mediator of miR-425-5p 's age-related functions in old oocytes. In vivo treatment with miR-425-5p antagomirs significantly improved impaired oocyte development in reproductively old females by targeting Crebzf . Single-cell RNA sequencing revealed that Crebzf plays a vital role in regulating mRNAs targeting histone H3, trimethylated lysine 4 (H3K4me3), a crucial marker for transcriptional silencing. Overexpression of miR-425-5p could hinder oocyte maturation by downregulating Crebzf expression and disrupting transcriptional regulation. Our findings provide new insights into the potential of miR-425-5p antagomirs as a treatment for female infertility and highlight an elegant mechanism by which miR-425-5p inhibition of Crebzf inhibits a developmental switch in GV oocytes by regulating a group of histone methyltransferase mRNAs.

Association of long-term particulate matter exposure with all-cause mortality among patients with ovarian cancer: A prospective cohort - Yi-Zi Li; Shu-Hong Huang; Su Shi; Wen-Xiao Chen; Yi-Fan Wei; Bing-Jie Zou; Wei Yao; Lu Zhou; Fang-Hua Liu; Song Gao; Shi Yan; Xue Qin; et al. (Science of The Total Environment, 2023)

Association of long-term exposure to ambient PM2.5 and its constituents with gut microbiota: Evidence from a China cohort - Sicheng Li; Bing Guo; Ke Dong; Shourui Huang; Jialong Wu; Hanwen Zhou; Kunpeng Wu; Xinyu Han; Xian Liang; Xiaofang Pei; Haojiang Zuo; Hualiang Lin; et al. (Science of The Total Environment, 2023)

Global phosphorus cycling: The impact of international commercial trading and the path towards sustainable phosphorus management - Sin Jin Ng; Bing Li; Zhengyang He; Jing-Cheng Han; Muhammad Tajammal Munir; Xiaofeng Wu; Yuefei Huang (Resources Policy, 2023)

Polyethylene mulch film-derived microplastics enhance the bioaccumulation of atrazine in two earthworm species (Eisenia fetida and Metaphire guillelmi) via carrier effects - Wenhui Song; Yankun Du; Dengtan Li; Zongyuan Xiao; Bing Li; Jinling Wei; Xinjie Huang; Chuanwei Zheng; Jinhua Wang; Jun Wang; Lusheng Zhu (Journal of Hazardous Materials, 2023)

Atmospheric humidity regulates same-sex mating in Candida albicans through the trehalose and osmotic signaling pathways - Chao Li; Li Tao; Guobo Guan; Zhangyue Guan; Austin M. Perry; Tianren Hu; Jian Bing; Ming Xu; Clarissa J. Nobile; Guanghua Huang (Science China Life Sciences, 2023)

Soil extracellular enzymes characteristics and their controlling factors along the elevation gradient in Qinghai-Tibet Plateau, China - Yan-xia Pan; Xin-rong Li; Zeng-ru Wang; Li Feng; Lei Huang; Bing-yao Wang; Jing-yao Sun (Applied Soil Ecology, 2023)

Two new isoflavones from the barks of Dalbergia hancei Benth - Xiao-Mei Li; Nao Pang; Ya-Feng Wang; Rui-Jie He; Li Ge; Bing-Yuan Yang; Ke-Di Yang; Yong-Lin Huang (Natural Product Research, 2023)

Buffering effect of the economizer against PCDD/Fs in flue gas from solid waste incineration plants - Jia-Wei Lu; Yingshi Xie; Bing Xie; Zhihong Li; Zhengpeng Huang; Dongfeng Zhang; Jing Hai (Waste Management, 2023)

Effect of sludge retention time (SRT) on micro-ecological niche competition kinetics between ammonia-oxidizing organisms (AOO) and nitrite-oxidizing organisms (NOO) in a single system - Yifan Li; Yuying Huang; Meng Sun; Jing Wang; Feiyong Chen; Yuanyuan Shao; Hidenari Yasui; Chenxi Sun; Rajeev Goel; Bing Liu (Journal of Water Process Engineering, 2023)

Adsorption of lead ions and methylene blue on acrylate-modified hydrochars - Yan Chen; Shen-Ao Huang; Kun Yu; Jian-Zhong Guo; Yu-Xuan Wang; Bing Li (Bioresource Technology, 2023)

Revisiting China's domestic greenhouse gas emission from wastewater treatment: A quantitative process life-cycle assessment - Dengting Guo; Bing Li; Wei Yu; Jing-Cheng Han; Yang Zhou; Zhilong Ye; Xiaofeng Wu; Brent Young; Yuefei Huang (Science of The Total Environment, 2023)

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

A low-diversity, silicified Hirnantia Fauna from Butuo, southwestern Sichuan, on the western margin of Yangtze Platform - Qian Wang; Bing Huang; Rongyu Li (Palaeoworld, 2023)

Improving sludge settling performance of secondary settling tank and simultaneously adsorbing nitrate and phosphate with surfactant modified zeolite (SMZ) ballasted flocculation - Hai Lin; Xijie Huang; Jiang Chang; Bing Li; Yongsheng Bai; Bojun Su; Luyuan Shi; Yingbo Dong (Journal of Environmental Chemical Engineering, 2023)

Synergistic promotion effect of acidity and redox capacity in the simultaneous removal of CB and NOx in NH3-SCR unit - Yifan Li; Yaqin Hou; Biao Li; Yatao Yang; Shuang Ma; Bing Wang; Zhanggen Huang (Fuel, 2023)

A review of the migration mechanism of antibiotics during struvite recovery from wastewater - Degui Gao; Bing Li; Xuewei Huang; Xiaoning Liu; Ruili Li; Zhilong Ye; Xiaofeng Wu; Yuefei Huang; Guangqian Wang (Chemical Engineering Journal, 2023)

Rapid granulation of aerobic granular sludge in an integrated moving bed biofilm reactor-membrane bioreactor: Effects and mechanism of Streptomyces cellulosus microspheres - Huanlong Zhang; Yue Xu; Liying Bin; Ping Li; Fenglian Fu; Shaosong Huang; Bing Tang (Bioresource Technology Reports, 2023)

Comparative insight into the effects of different carbon source supplement on antibiotic resistance genes during whole-run and short-cut nitrification-denitrification processes - Meilan Zhang; Kaiyi Li; Panliang Wang; Wenchao Gu; Huang Huang; Bing Xie (Environmental Science and Pollution Research, 2023)

Quantifying the effects of submicroscopic metallic iron on VIS–NIR spectra of lunar soils - Yanhua Peng; Siting Zhang; Hong Tang; Zhuang Guo; Wen Yu; Guozhu Chen; Chen Li; Bingkui Miao; Bing Mo; Encheng He; Ting Zhou; Zhipeng Xia; et al. (Icarus, 2023)

Improving the biodegradation of chicken feathers by a Bacillus licheniformis ZSZ6 mutant and application of hydrolysate - Chunhong Cui; Liqiong Sun; Xuelian Chen; Yu Zhu; Zhi Zheng; Dongmei Mao; Mingxu Li; Yuxin Li; Yajun Cao; Bing Feng; Hui Wang; Lin Wang; et al. (International Biodeterioration & Biodegradation, 2023)

Distribution and co-occurrence of antibiotic resistance genes and bacterial pathogens in the effluent of decentralized sewage treatment systems in China - Dawei Huang; Bing Li; Yong Qiu; Ji Li (International Biodeterioration & Biodegradation, 2023)

RETRACTED: Determining the spatial non-stationarity underlying social and natural environment in thyroid cancer in China - Xiyu Zhang; Yongqiang Lai; Xiaodan Bai; Bing Wu; Wenjing Xiang; Chenxi Zhang; Guihong Geng; Wenqing Miao; Qi Xia; Qunhong Wu; Huiying Yang; Yanjie Wang; et al. (Science of The Total Environment, 2023)

Efficient Bayesian method for characterizing multiple soil parameters using parametric bootstrap - Xiao-Song Tang; Han-Bing Huang; Xiong-Feng Liu; Dian-Qing Li; Yong Liu (Computers and Geotechnics, 2023)

Unraveling Photothermal-Enhanced bulk charge transport and surface oxygen reactions in TiO2 photoanodes for highly efficient photoelectrochemical water oxidation - Jing Huang; Xiaoqin Hu; Jingnan Wang; Kaijie Lin; Bing He; Yingkui Yang; Yang Wang; Zhen Li; Xueqin Liu (Chemical Engineering Journal, 2023)

Research on synthesis and property of nano-textured Sc2O3-MgO efficient antibacterial agents - Ying Wang; Yanjing Liu; Xiyue Li; Yuezhou Liu; Fuming Wang; Yaping Huang; Bing Du; Yongfang Qian; Lihua Lv (JBIC Journal of Biological Inorganic Chemistry, 2023)

Effect of florasulam on oxidative damage and apoptosis in larvae and adult zebrafish (Danio rerio) - Xiaole Wang; Jingwen Zhang; Yu Liu; Chengbo Lu; Kaixuan Hou; Yunchen Huang; Albert Juhasz; Lusheng Zhu; Zhongkun Du; Bing Li (Journal of Hazardous Materials, 2023)

Catalytic modification of corn straw facilitates the remediation of Cd contaminated water and soil - Jie Huang; Yunhong Jiao; Anthony J. Weatherley; Alex Xiaofei Duan; Shutao Wang; Chaoyu Li; Zhiling Ma; Wei Liu; Bing Han (Journal of Hazardous Materials, 2023)

Enabling efficiency-driven and low-impact water management from robust decision making: A risk- and robustness-based multi-objective decision support model - Yang Zhou; Bing Li; Jingcheng Han; Guojian He; Keyi Wang; Chunjiang An; Yuefei Huang (Journal of Cleaner Production, 2023)

Flood risk assessment by using an interpretative structural modeling based Bayesian network approach (ISM-BN): An urban-level analysis of Shenzhen, China - Guyuan Li; Xiaofeng Wu; Jing-Cheng Han; Bing Li; Yuefei Huang; Yongqiang Wang (Journal of Environmental Management, 2023)

Potential of kerosene-diesel blends as alternative fuels for diesel engines: Perspectives from spray combustion characteristics - Zhaowen Wang; Xiaojie Li; Lin Xiang; Yuhan Huang; Bing Lang; Xiaobei Cheng; Jie Zhang (Fuel, 2023)

Survey of the biogenic amines in craft beer from the Chinese market and the analysis of the formation regularity during beer fermentation - Chenyu Li; Xiaoyu Han; Bing Han; Huan Deng; Tianyang Wu; Xiaoxuan Zhao; Weidong Huang; Jicheng Zhan; Yilin You (Food Chemistry, 2023)

Performance and application of a novel drainage anti-slide pile on accumulation landslide with a chair-like deposit-bedrock interface in the Three Gorges Reservoir area, China - Shi-lin Luo; Da Huang; Jian-bing Peng; Ailifeila Aierken; Zhao Li; Xi-bin Kuang; Roberto Tomás (Computers and Geotechnics, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

Network evolution and risk assessment of the global phosphorus trade - Bing Li; Sin Jin Ng; Jing-Cheng Han; Manjie Li; Jiewei Zeng; Dengting Guo; Yang Zhou; Zhengyang He; Xiaofeng Wu; Yuefei Huang (Science of The Total Environment, 2023)

Distinct contribution of aqueous solutions and hydrous melts to the mantle sources: Geochemical evidence from Late Paleozoic igneous rocks in Southwestern Tianshan, Western China - Li-Tao Ma; Li-Qun Dai; Zi-Fu Zhao; Fang Huang; Bing Gong (Lithos, 2023)

Spectral change of dissolved organic matter after extracted by solid-phase extraction and its feasibility in predicting the acute toxicity of polar organic pollutants in textile wastewater - Lingfang Fu; Liying Bin; Zhaobo Luo; Zehong Huang; Ping Li; Shaosong Huang; Dieudonne Nyobe; Fenglian Fu; Bing Tang (Journal of Hazardous Materials, 2023)

Structural and energetic basis of interaction between human estrogen-related receptor γ and environmental endocrine disruptors from multiple molecular dynamics simulations and free energy predictions - Lin Chen; Xu Huang; Yufei Li; Bing Zhao; Min Liang; Ruige Wang (Journal of Hazardous Materials, 2023)

Solvent-free oxidation of toluene to benzaldehyde using electron-rich Au clusters confined in Silicalite-1 - He Huang; Huahua Fan; Yuzhen Ge; Wanyue Ye; Yingcen Liu; Caicheng Song; Hua Lin; Xiaotong Zhang; Bing Li; Xiaowa Nie; Shufen Zhang; Rongwen Lu (Chemical Engineering Journal, 2023)

Porewater dissolved inorganic carbon released due to artificial sediment scouring in the Yellow River - Xing-yu Huang; Dong Zhang; Fu-shun Wang; Zhi-qi Zhao; Ai-chun Chen; Jun-wen Zhang; Cong Zhang; Li Wu; Yu-hong Li; Bing-juan Ma; Qi-yan Feng (Applied Geochemistry, 2023)

Dye mineralization under UV/H2O2 promoted by chloride ion at high concentration and the generation of chlorinated byproducts - Bing Yang; Qiuping Luo; Qinman Li; Rong Jia; Yucheng Liu; Xiangfu Huang; Mi Zhou; Lingli Li (Science of The Total Environment, 2023)

Life cycle cost analysis of solar energy via environmental externality monetization - Beijia Huang; Yuyue Wang; Ying Huang; Xiaozhen Xu; Xian Chen; Lian Duan; Guoqing Yu; Zeqiu Li; Hongzhi Liu; Harn Wei Kua; Bing Xue (Science of The Total Environment, 2023)

New insights into lincomycin biodegradation by Conexibacter sp. LD01: Genomics characterization, biodegradation kinetics and pathways - Huaxin Lei; Jiayu Zhang; Jin Huang; Dengjin Shen; Yin Li; Rui Jiao; Renxin Zhao; Xiaoyan Li; Lin Lin; Bing Li (Journal of Hazardous Materials, 2023)

Utilization of activated sludge and shell wastes for the preparation of Ca-loaded biochar for phosphate removal and recovery - Jing Li; Lu Cao; Bing Li; Haiming Huang; Wei Yu; Cairui Sun; Kehua Long; Brent Young (Journal of Cleaner Production, 2023)

Effect of gradual increase of atmospheric CO2 concentration on nitrification potential and communities of ammonia oxidizers in paddy fields - Bing-jie Ren; Li-dong Shen; Xin Liu; Jing-hao Jin; He-chen Huang; Mao-hui Tian; Yu-ling Yang; Wang-ting Yang; Jia-qi Liu; Cai-yu Geng; Hong-sheng Wu; Zheng-hua Hu (Journal of Environmental Management, 2023)

Novel multifunctional natural selenium supplement development, in vitro and in vivo analysis, and risk-benefit assessment: Selenium-enriched chicory as a case study - Yaolei Li; Shanshan Ju; Jinjian Huang; Hao Wu; Zhijian Lin; Yu Wang; Hongyu Jin; Shuangcheng Ma; Bing Zhang (Journal of Cleaner Production, 2023)

Thermally reversible Mesona chinensis polysaccharide hydrogel - Siyuan Huang; Weijuan Huang; Qiantong Gu; Jiayuan Luo; Kun Wang; Bing Du; Pan Li (Food Hydrocolloids, 2023)

Hypervalent potassium xanthate modified SnO2 for highly efficient perovskite solar modules - Pin Lv; Yufei Yang; Neng Li; Yuxi Zhang; Min Hu; Bo Huang; Yanqing Zhu; Yulong Wang; Junye Pan; Shifeng Wang; Bo Zhang; Fuzhi Huang; et al. (Chemical Engineering Journal, 2023)

Evolving a high-performance bio-imaging tool derived from a compact fluorophore as well as creating a reaction-based fluorescent probe for precise determination of Ag+ - Zi Yi Xu; Xiao Hu Wang; Sha Li Huang; Jing Rong Chen; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2023)

Correction to: Ketone Body Rescued Seizure Behavior of LRP1 Deficiency in Drosophila by Modulating Glutamate Transport - Jin-Ming Zhang; Ming-Jie Chen; Jiong-Hui He; Ya-Ping Li; Zhi-Cai Li; Zi-Jing Ye; Yong-Hui Bao; Bing-Jun Huang; Wen-Jie Zhang; Ping Kwan; Yu-Ling Mao; Jing-da Qiao (Journal of Molecular Neuroscience, 2023)

Exploring the Wenchuan earthquake fault through the accurate location of WFSD-4# Well using seismic reflection - Yang-Yang Feng; Chang-Qing Yu; Hai-Bing Li; Chen Qu; Chan Wu; Qi Wang; Su Luo; Jin-Peng Huang; Ghazi Rehana (Applied Geophysics, 2022)

Hydrocarbons removal and microbial community succession in petroleum-contaminated soil under hydrogen peroxide treatment - Bing Yang; Mi Zhou; Yuan Meng; Keming Chen; Jie Xu; Xiangfu Huang; Yucheng Liu; Lingli Li; Lili Ma; Mingyan Chen (Environmental Science and Pollution Research, 2022)

Response of the metabolic and autophagy pathways in Mytilus under starvation - Bing Xie; Chuan-yue Chen; Xiaolin Zhang; Si-yuan Li; Zhong-qi Gu; Ji Huang; Jian-yu He; Peng-zhi Qi; Bao-ying Guo; Zhi Liao; Xiaojun Yan (Frontiers in Marine Science, 2022)
Being an industrially valuable species of bivalve, Mytilus is widespread in the area around the eastern coast of China. Starvation is an environmental stress that mussels often encounter in their growth. However, few report carried out on the physiological and biochemical response and molecular regulation and adaptation mechanism of mussels under starvation. To illustrate the molecular mechanism of hosts of Mytilus to starvation, the gill transcriptome was used for analysis before and after 9 days of starvation in Mytilus using the Illumina/HiSeq-2000 deep sequencing platform, accompanied by the study of differentially expressed genes (DEGs). In total, 42.137 GB of clean data were obtained from six sample libraries, the average amount of clean data of each sample is 7.023 GB, and 58,540 unigenes that average 780 bp in length were assembled. Unigenes were illustrated by commenting them against the NR, Swiss-Prot, Pfam, String, GO and KEGG databases. After 9 days of starvation, 2,188 and 2,672 genes were determined to be significantly up- or down-regulated expression genes, separately. Amongst, 4,860 genes were associated with 260 pathways, contains vital enrichment pathways, such as “Metabolic”, “PI3K-Akt signaling pathway”, “Phagosome”, “Apoptosis” and “Lysosome”. In inclusion, autophagy cells were investigated by an electron microscopy, alongside further observations of the expression of autophagy-related genes in gill tissue before and after starvation. The data indicates that the amount of autophagosomes increased and found that atg2 , atg6 and atg13 were significantly up-regulated. These results indicated that Mytilus may use autophagy to cope with their damage after starvation. With our research results, we have contributed to a deeper understanding of the role of the molecular mechanisms of immune defence in Mytilus under environmental stress, which has given insights into mussel breeding and the understanding of the molecular mechanisms of Mytilus immune system.

Xylomexicanins K-N: limonoids from the leaves and twigs of Xylocarpus granatum - Shao-Jing Li; Li-Kang Zhao; Jin-Jun Chen; Chun-Hua Zhou; Xin-Li Huang; Yi-Bing Wu; Françoise Sauriol; Yu-Cheng Gu; Hiromasa Kiyota (Natural Product Research, 2022)

REGγ drives Lgr5+ stem cells to potentiate radiation induced intestinal regeneration - Xiangzhan Zhu; Minglei Yang; Zaijun Lin; Solomon Kibreab Mael; Ya Li; Lili Zhang; Yaqi Kong; Yaodong Zhang; Yuping Ren; Jianhui Li; Zimeng Wang; Ying Zhang; et al. (Science China Life Sciences, 2022)

Development of Physiology Based Pharmacokinetic Model to Predict the Drug Interactions of Voriconazole and Venetoclax - Ji Dong; Shuai-bing Liu; Jony Md Rasheduzzaman; Chen-rong Huang; Li-yan Miao (Pharmaceutical Research, 2022)

Ketone Body Rescued Seizure Behavior of LRP1 Deficiency in Drosophila by Modulating Glutamate Transport - Jin-Ming Zhang; Ming-Jie Chen; Jiong-Hui He; Ya-Ping Li; Zhi-Cai Li; Zi-Jing Ye; Yong-Hui Bao; Bing-Jun Huang; Wen-Jie Zhang; Ping Kwan; Yu-Ling Mao; Jing-da Qiao (Journal of Molecular Neuroscience, 2022)

Dietary phosphorus requirement for juvenile bighead carp (Aristichthys nobilis) - Meifeng Li; Li Zhang; Bing Hu; Lei Liu; Feng Huang; Juan Tian; Xianqin Hu; Yuanyuan Wang (Aquaculture International, 2022)

In situ stress state and seismic hazard in the Dayi seismic gap of the Longmenshan thrust belt - Bing Li; Furen Xie; Jinshui Huang; Xiwei Xu; Qiliang Guo; Guangwei Zhang; Junshan Xu; Jianxin Wang; Dawei Jiang; Jian Wang; Lifeng Ding (Science China Earth Sciences, 2022)

Neuropeptide FF-related gene in fish (Larimichthys polyactis): identification, characterization, and potential anti-inflammatory function - Ran Xiao; Zuting Guo; Li-bing Zheng; Wei Huang; Chang-feng Chi; Bao Lou (Molecular Biology Reports, 2022)

Increases in temperature response to CO2 emissions in biochar-amended vegetable field soil - Rong Huang; Zifang Wang; Yi Xiao; Luo Yu; Xuesong Gao; Changquan Wang; Bing Li; Qi Tao; Qiang Xu; Ming Gao (Environmental Science and Pollution Research, 2022)

Anti-inflammatory and antioxidant activities of chemical constituents from the flower buds of Buddleja officinalis - Fei-Bing Huang; Na Liang; Nusrat Hussain; Xu-Dong Zhou; Muhammad Ismail; Qing-Ling Xie; Huang-He Yu; Yu-Qing Jian; Cai-Yun Peng; Bin Li; Bin Liu; Sheng-Huang Chen; et al. (Natural Product Research, 2022)

Vanadium recovery by glycine precipitation - Hao Peng; Chenyu Zhang; Zhihui Hao; Songting Jiang; Jing Guo; Huisheng Huang; Bing Li (Environmental Chemistry Letters, 2022)

Removal and recovery of vanadium from waste by chemical precipitation, adsorption, solvent extraction, remediation, photo-catalyst reduction and membrane filtration. A review - Hao Peng; Jing Guo; Bing Li; Huisheng Huang; Wenbing Shi; Zuohua Liu (Environmental Chemistry Letters, 2022)

Supplementation of Bacillus sp. DU-106 Alleviates Antibiotic-Associated Diarrhea in Association with the Regulation of Intestinal Microbiota in Mice - Darong Huang; Yanlan Chen; Hongzhu Chen; Xinyu Deng; Jianzhao Huang; Siming Lu; Pan Li; Bing Du (Probiotics and Antimicrobial Proteins, 2022)

Vanadium properties, toxicity, mineral sources and extraction methods: a review - Hao Peng; Jing Guo; Bing Li; Huisheng Huang (Environmental Chemistry Letters, 2022)

Association of long-term exposure to ambient air pollution with the number of tuberculosis cases notified: a time-series study in Hong Kong - Man Xu; Ping Hu; Ruoling Chen; Bing Liu; Hongying Chen; Jian Hou; Li ke; Jiao Huang; Hairong Ren; Hui Hu (Environmental Science and Pollution Research, 2022)

Spatial–temporal evolution pattern and prediction analysis of flood disasters in China in recent 500 years - Cuixia Wei; Bing Guo; Hailing Zhang; Baomin Han; Xiangshen Li; Huihui Zhao; Yuefeng Lu; Chao Meng; Xiangzhi Huang; Wenqian Zang; Hongwei Wu (Earth Science Informatics, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Endogenic upregulations of HIF/VEGF signaling pathway genes promote air breathing organ angiogenesis in bimodal respiration fish - Songqian Huang; Lijuan Yang; Li Zhang; Bing Sun; Jian Gao; Zijian Chen; Lei Zhong; Xiaojuan Cao (Functional & Integrative Genomics, 2022)

Rice functional genomics: decades’ efforts and roads ahead - Rongzhi Chen; Yiwen Deng; Yanglin Ding; Jingxin Guo; Jie Qiu; Bing Wang; Changsheng Wang; Yongyao Xie; Zhihua Zhang; Jiaxin Chen; Letian Chen; Chengcai Chu; et al. (Science China Life Sciences, 2022)

Experimental mechanical strength and deformation characteristics of deep damaged–fractured rock - Qing-Bin Meng; Jiang-Feng Liu; Li-Xiang Xie; Hai Pu; Yu-Gui Yang; Bing-Xiang Huang; Wei Qian (Bulletin of Engineering Geology and the Environment, 2022)

Adult-repopulating lymphoid potential of yolk sac blood vessels is not confined to arterial endothelial cells - Chaojie Wang; Yandong Gong; Anbang Wei; Tao Huang; Siyuan Hou; Junjie Du; Zongcheng Li; Junliang Wang; Bing Liu; Yu Lan (Science China Life Sciences, 2021)

Alkaloids with acetylcholinesterase inhibitory activity from Corydalis racemosa (Thunb.) Pers - Hui-Na Yao; Zhi-Tian Peng; Yun-Feng Zhang; Di-Fa Liu; Bing-Feng Huang; Peng-Fei Tu; Yun-Fang Zhao; Hui-Xia Huo; Jun Li (Natural Product Research, 2021)

Two New Zn(II)/Cu(II) Compounds: Photoluminescent and Photocatalytic Properties, and Protective Activity on Parkinson Disease - Ning Wang; Fang-Jie Huang; Mang-Suo Zhao; Bing-Xin Shi; Yan Wei; Li-Yan Qiao (Journal of Fluorescence, 2021)

Exposure to 2,4-dichlorophenol, 2,4,6-trichlorophenol, pentachlorophenol and risk of thyroid cancer: a case-control study in China - Wan-Jun Yang; Hua-Bing Wu; Chi Zhang; Qi Zhong; Ming-Jun Hu; Jia-Liu He; Guo-Ao Li; Zhen-Yu Zhu; Jin-Liang Zhu; Huan-Huan Zhao; Han-Shuang Zhang; Fen Huang (Environmental Science and Pollution Research, 2021)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

Urban trees in university campus: structure, function, and ecological values - Xueyan Wang; Yanlin Wang; Xiaohan Qu; Bing Huang; Zeming Li; Junjiao Sun; Xiaoqing Wei; Xiuying Yang (Environmental Science and Pollution Research, 2021)

Effects of drought and heat on the productivity and photosynthetic characteristics of alpine meadow plants on the Qinghai-Tibetan Plateau - Li Ma; Zhong-hua Zhang; Bu-qing Yao; Zhen Ma; Xiao-tao Huang; Bing-rong Zhou; Man-hou Xu; Jing Guo; Hua-kun Zhou (Journal of Mountain Science, 2021)

DNA Methyltransferase 1 Is Dysregulated in Parkinson’s Disease via Mediation of miR-17 - Hong-Qiu Zhang; Jian-Yong Wang; Zhao-Feng Li; Lei Cui; Shi-Shi Huang; Lan-Bing Zhu; Yue Sun; Rui Yang; Hui-Hui Fan; Xiong Zhang; Jian-Hong Zhu (Molecular Neurobiology, 2021)

A Decision-Making Method for Autonomous Collision Avoidance for the Stand-On Vessel Based on Motion Process and COLREGs - Bing Wang; Yixiong He; Weixuan Hu; Junmin Mou; Liling Li; Ke Zhang; Liwen Huang (Journal of Marine Science and Engineering, 2021)
A great number of collision accidents can be attributed to incongruous collision-avoidance actions between the give-way vessel and the stand-on vessel in a crossing or overtaking situation. If the give-way vessel does not take appropriate collision-avoidance action according to international regulations for preventing collisions at sea, the last barrier to pass safely is the appropriate and effective collision-avoidance action taken by the stand-on vessel. To find the proper autonomous collision-avoidance action of the stand-on vessel, a method is proposed that combines quantitative analysis rules of collision-avoidance with the deduction of nonlinear maneuvering motion process based on the mathematical model group, which conformity can reach 90%. This research presents a method to calculate the timing and most effective collision-avoidance actions for the stand-on vessel based on the four-stage theory of encountering vessels and the characteristics of vessel motion. The accuracy of the latest-action timing and the action amplitude for the stand-on vessel can be increased to the level of second and degree, respectively. A novel model of collision risk index is constructed by the latest time of the feasible collision-avoidance action on the precise of different course-altering amplitude. Methods to find the stand-on vessel’s proper collision-avoidance actions in the open sea are presented. The simulation indicates the proposed method for the stand-on vessel can make correct collision-avoidance decisions autonomously.

Steady increase in water clarity in Jiaozhou Bay in the Yellow Sea from 2000 to 2018: Observations from MODIS - Ziyao Yin; Junsheng Li; Jue Huang; Shenglei Wang; Fangfang Zhang; Bing Zhang (Journal of Oceanology and Limnology, 2021)

Human β-Defensin 118 Attenuates Escherichia coli K88–Induced Inflammation and Intestinal Injury in Mice - Qian Lin; Qingqing Fu; Xiang Li; Yuheng Luo; Junqiu Luo; Daiwen Chen; Xiangbing Mao; Bing Yu; Ping Zheng; Zhiqing Huang; Jie Yu; Hui Yan; et al. (Probiotics and Antimicrobial Proteins, 2021)

Recovery of chromium by calcium-roasting, sodium-roasting, acidic leaching, alkaline leaching and sub-molten technology: a review - Hao Peng; Jing Guo; Liping Lv; Huisheng Huang; Bing Li (Environmental Chemistry Letters, 2021)

New cytotoxic biflavones from Selaginella doederleinii - Li-Fei Liu; Hui-Hui Sun; Jian-Bing Tan; Qi Huang; Fei Cheng; Kang-Ping Xu; Zhen-Xing Zou; Gui-Shan Tan (Natural Product Research, 2021)

Numerical investigation of the thermal effect on flow and dispersion of rooftop stack emissions with wind tunnel experimental validations - Yuan-Dong Huang; Nuo Xu; Su-Qi Ren; Li-Bing Qian; Peng-Yi Cui (Environmental Science and Pollution Research, 2021)

Enrichment of cadmium in rice (Oryza sativa L.) grown under different exogenous pollution sources - Yi-Min Zhou; Si-Si Long; Bing-Yu Li; Ya-Yuan Huang; Yong-Jie Li; Jia-Yan Yu; Hui-Hui Du; Sardar Khan; Ming Lei (Environmental Science and Pollution Research, 2020)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

Effects of Increased Carbon Supply on the Growth, Nitrogen Metabolism and Photosynthesis of Vallisneria natans Grown at Different Temperatures - Heng Jiang; Bing Huang; Zhan Qian; Yue Xu; Xiaohong Liao; Ping Song; Xichun Li (Wetlands, 2020)

Genetic diversity comparisons of wild populations of Nelumbo nucifera (Nelumbonaceae) in Russia and China using microsatellite markers - Zhi-Zhong Li; Md. Rabiul Islam; Shi-Xu Huang; Dan Yang; Yeshitila Mekbib; Popova Svetlana; Hong-Bing Sun; Jin-Ming Chen; Xing-Yu Yang (Plant Systematics and Evolution, 2020)

Ginsenosides in root exudates of Panax notoginseng drive the change of soil microbiota through carbon source different utilization - Li-Fen Luo; Lei Yang; Zheng-Xu Yan; Bing-Bing Jiang; Su Li; Hui-Chuan Huang; Yi-Xiang Liu; Shu-Sheng Zhu; Min Yang (Plant and Soil, 2020)

Identification and genome characterization of a novel picornavirus from ducks in China - Yufeng Li; Kaicheng Wang; Kexiang Yu; Feng Hu; Xue Tian; Bing Huang; Hualei Liu; Jiaqiang Wu; Minxun Song (Archives of Virology, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Local wind characteristics on bridge deck of twin-box girder considering wind barriers by large-scale wind tunnel tests - Jingyu Zhang; Mingjin Zhang; Yongle Li; Yizhe Qian; Bing Huang (Natural Hazards, 2020)

Acanthophoraine A, a new pyrrolidine alkaloid from the red alga Acanthophora spicifera - Jia-Li Lin; Yong-Qian Liang; Xiao-Jian Liao; Jian-Ting Yang; Dai-Chun Li; Yu-Ling Huang; Zhi-Hui Jiang; Shi-Hai Xu; Bing-Xin Zhao (Natural Product Research, 2020)

Synergistic Effect of Rhamnolipids and Inoculation on the Bioremediation of Petroleum-Contaminated Soils by Bacterial Consortia - Shu-wen Xue; Chao Huang; Yue-xin Tian; Yan-bing Li; Jing Li; Yan-ling Ma (Current Microbiology, 2020)

Ribosome profiling analysis identified a KRAS-interacting microprotein that represses oncogenic signaling in hepatocellular carcinoma cells - Wenli Xu; Bing Deng; Penghui Lin; Chang Liu; Bin Li; Qiaojuan Huang; Hui Zhou; Jianhua Yang; Lianghu Qu (Science China Life Sciences, 2020)

Next-generation sequencing technology as a powerful detection and semi-quantitative method for herpes simplex virus type 1 in pediatric encephalitis - Lin-lin Liu; Ling-yun Guo; Jie Dong; Wen-hua Huang; Li Zhao; Bing Liu; Xi-xi Zhang; Yong-qiang Jiang; Gang Liu (Journal of NeuroVirology, 2020)

Chloroplast genome of an extremely endangered conifer Thuja sutchuenensis Franch.: gene organization, comparative and phylogenetic analysis - Tao Yu; Bing-Hong Huang; Yuyang Zhang; Pei-Chun Liao; Jun-Qing Li (Physiology and Molecular Biology of Plants, 2020)

Characteristics and Prognosis of Talaromyces marneffei Infection in Non-HIV-Infected Children in Southern China - Jing Guo; Bing-Kun Li; Tian-Min Li; Fang-Lin Wei; Yu-Jiao Fu; Yan-Qing Zheng; Kai-Su Pan; Chun-Yang Huang; Cun-Wei Cao (Mycopathologia, 2019)

Effects of Officials’ Cross-Regional Redeployment on Regional Environmental Quality in China - Bing Zhou; Yumeng Li; Xiaoli Lu; Shengzhong Huang; Bing Xue (Environmental Management, 2019)

Proteome analysis of reticuloendotheliosis-virus-infected chicken embryo fibroblast cells through iTRAQ-based quantitative proteomics - Feng Hu; Yufeng Li; Kexiang Yu; Xiuli Ma; Cunxia Liu; Xiaozhen Guo; Minxun Song; Jiaqiang Wu; Bing Huang (Archives of Virology, 2019)

First report of sheath rot caused by Fusarium proliferatum on Pisang Awak Banana (Musa ABB) in China - Sui-Ping Huang; Ji-Guang Wei; Tang-Xun Guo; Qi-Li Li; Li-Hua Tang; Jian-You Mo; Ji-Feng Wei; Xiao-Bing Yang (Journal of Plant Pathology, 2019)

Improved recombinant protein production by regulation of transcription and protein transport in Chinese hamster ovary cells - Kaiming Chen; Dong Li; Hongwen Li; Bing Li; Ruiqin Wang; Lingxiao Jiang; Lei Huang; Xiaoqing Xu; Jie Li; Fei Teng; Cizhong Jiang; Hua Gu; et al. (Biotechnology Letters, 2019)

Daedaleanols A and B, two new sesquiterpenes from cultures of the basidiomycete Daedalea incana - Ying Huang; Shuai-Bing Zhang; He-Ping Chen; Zhen-Zhu Zhao; Zheng-Hui Li; Tao Feng; Ji-Kai Liu (Natural Product Research, 2019)

Silurian integrative stratigraphy and timescale of China - Jiayu Rong; Yi Wang; Renbin Zhan; Junxuan Fan; Bing Huang; Peng Tang; Yue Li; Xiaole Zhang; Rongchang Wu; Guangxu Wang; Xin Wei (Science China Earth Sciences, 2019)

Variability of East Asian summer monsoon precipitation during the Holocene and possible forcing mechanisms - Fuzhi Lu; Chunmei Ma; Cheng Zhu; Huayu Lu; Xiaojian Zhang; Kangyou Huang; Tianhong Guo; Kaifeng Li; Lan Li; Bing Li; Wenqing Zhang (Climate Dynamics, 2019)

Complete Genome Sequence of Clostridium kluyveri JZZ Applied in Chinese Strong-Flavor Liquor Production - Yansheng Wang; Bin Li; Hong Dong; Xunduan Huang; Ruiyu Chen; Xingjie Chen; Laoji Yang; Bing Peng; Guopai Xie; Wei Cheng; Biao Hao; Changrun Li; et al. (Current Microbiology, 2018)

Enhanced catalytic activities and modified substrate preferences for taxoid 10β-O-acetyl transferase mutants by engineering catalytic histidine residues - Lin-Feng You; Jia-Jun Huang; Tao Wei; Shu-Ling Lin; Bing-Hua Jiang; Li-Qiong Guo; Jun-Fang Lin (Biotechnology Letters, 2018)

Rapid and sensitive determination of furaltadone metabolite 3-amino-5-morpholinomethyl-2-oxazolidinone by biotin–streptavidin-amplified time-resolved fluoroimmunoassay - Yi Zhang; Chunhui Zhao; Bing Wu; Ying Li; Fang Lv; Jue Zhang; Bin Zhou; Jun Fan; Biao Huang (Fisheries Science, 2018)

Molecular surveillance of Vittaforma-like microsporidia by a small-volume procedure in drinking water source in Taiwan: evidence for diverse and emergent pathogens - Jung-Sheng Chen; Bing-Mu Hsu; Hsin-Chi Tsai; Yu-Pin Chen; Tung-Yi Huang; Kuan-Ying Li; Dar-Der Ji; Herng-Sheng Lee (Environmental Science and Pollution Research, 2018)

Effects of environment and genotype on mercury and methylmercury accumulation in rice (Oryza sativa L.) - Lu Huang; Bing Li; Nora Fung-Yee Tam; Xun Wang; Zhihong Ye (Plant and Soil, 2018)

Early warning model for slope debris flow initiation - Ming-li Li; Yuan-jun Jiang; Tao Yang; Qiang-bing Huang; Jian-ping Qiao; Zong-ji Yang (Journal of Mountain Science, 2018)

Origin and effect factors of sedimentary organic carbon in a karst groundwater-fed reservoir, South China - Siyu Huang; Junbing Pu; Jianhua Cao; Jianhong Li; Tao Zhang; Feng Jiang; Li Li; Feihong Wu; Moucheng Pan; Bing Bai (Environmental Science and Pollution Research, 2018)

Complete genome sequence of shrimp hemocyte iridescent virus (SHIV) isolated from white leg shrimp, Litopenaeus vannamei - Liang Qiu; Meng-Meng Chen; Ruo-Yu Wang; Xiao-Yuan Wan; Chen Li; Qing-Li Zhang; Xuan Dong; Bing Yang; Jian-Hai Xiang; Jie Huang (Archives of Virology, 2018)

TNF-α/TNFR1 Signaling is Required for the Full Expression of Acute and Chronic Itch in Mice via Peripheral and Central Mechanisms - Xiuhua Miao; Ya Huang; Teng-Teng Liu; Ran Guo; Bing Wang; Xue-Long Wang; Li-Hua Chen; Yan Zhou; Ru-Rong Ji; Tong Liu (Neuroscience Bulletin, 2018)

ThPP1 gene, encodes an inorganic pyrophosphatase in Thellungiella halophila, enhanced the tolerance of the transgenic rice to alkali stress - Rui He; Guohong Yu; Xiaori Han; Jiao Han; Wei Li; Bing Wang; Shengcai Huang; Xianguo Cheng (Plant Cell Reports, 2017)

Biosynthesis and functions of metabolites - Juncong Sun; Bing Leng; Guoan Sheng; Xin Fang; Laigeng Li; Jirong Huang; Xiaoquan Qi; Xiaoya Chen (Science China Life Sciences, 2017)

Complete genomic sequence of a duck enteritis virus attenuated via serial passage in chick embryos - Chenghuai Yang; Bing Zhang; Junping Li; Xiaojie Huang; Dan Liu; Lidan Hou; Qihong Li; Huijiao Li (Archives of Virology, 2017)

Ran binding protein 9 (RanBPM) binds IFN-λR1 in the IFN-λ signaling pathway - Junwen Zhang; Xiaojie Cong; Jiajie Zhaoqiao; Xia Yang; Meng Li; Hong Chen; Ruifang Mi; Guishan Jin; Fusheng Liu; Bing-Ren Huang (Science China Life Sciences, 2017)

Two new biphenyls from the stems of Garcinia tetralata - Bing-Kun Ji; Xue-Mei Gao; Di Cui; Shan-Shan Wang; Wen-Zhong Huang; Yin-Ke Li; Shuang-Xi Mei; Zhi Yang; Gan-Peng Li; Meng-Yuan Jiang; Yong-Hui He; Zhi-Yong Jiang; et al. (Natural Product Research, 2017)

DNA hypermethylation of sFRP5 contributes to indoxyl sulfate-induced renal fibrosis - Yanlin Yu; Xu Guan; Ling Nie; Yong Liu; Ting He; Jiachuan Xiong; Xinli Xu; Yan Li; Ke Yang; Yiqin Wang; Yunjian Huang; Bing Feng; et al. (Journal of Molecular Medicine, 2017)

Effects of DDIT4 in Methamphetamine-Induced Autophagy and Apoptosis in Dopaminergic Neurons - Bing Li; Rui Chen; Ling Chen; Pingming Qiu; Xiuyun Ai; Enping Huang; Weiye Huang; Chuanxiang Chen; Chao Liu; Zhoumeng Lin; Wei-Bing Xie; Huijun Wang (Molecular Neurobiology, 2017)

Complete genomic characterization of two European-genotype porcine reproductive and respiratory syndrome virus isolates in Fujian province of China - Jian-Kui Liu; Chun-Hua Wei; AI-Ling Dai; Ke-Wei Fan; Bing-Hui Yang; Chun-Fang Huang; Xiao-Hua Li; Xiao-Yan Yang; Man-Lin Luo (Archives of Virology, 2017)

Identification of russet-associated microRNAs in the exocarp of a Dangshansuli pear mutant (Pyrus bretschneideri Rehd.) by high-throughput sequencing - Wei Heng; Bing Jia; Hai-na Huang; Jin-yu Yang; Zi-teng Wang; Pu Liu; Li Liu; Zhen-feng Ye; Li-wu Zhu (Tree Genetics & Genomes, 2016)

A comparative study of strontium-substituted hydroxyapatite coating on implant’s osseointegration for osteopenic rats - Zhou-Shan Tao; Bing-Li Bai; Xing-Wen He; Wei Liu; Hang Li; Qiang Zhou; Tao Sun; Zheng-Liang Huang; Kai-kai Tu; Yang-Xun Lv; Wei Cui; Lei Yang (Medical & Biological Engineering & Computing, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Transcriptional regulation of mast cell and basophil lineage commitment - Hua Huang; Yapeng Li; Bing Liu (Seminars in Immunopathology, 2016)

Water-oats harbors two strains of the striped stem borer Chilo suppressalis (Lepidoptera: Crambidae) with temporal divergence in mating behavior - Chen Huang; Bing Hu; Jianhong Li; Yongmo Wang (Applied Entomology and Zoology, 2016)

A new cytotoxic biflavonoid from the rhizome of Wikstroemia indica - Meng Shao; Xiao-Jun Huang; Jun-Shan Liu; Wei-Li Han; Hong-Bing Cai; Qing-Fa Tang; Qin Fan (Natural Product Research, 2016)

Phylogenetic relationship of two popular edible Pleurotus in China, Bailinggu (P. eryngii var. tuoliensis) and Xingbaogu (P. eryngii), determined by ITS, RPB2 and EF1α sequences - Xiao-Lan He; Bo Wu; Qian Li; Wei-Hong Peng; Zhong-Qian Huang; Bing-Cheng Gan (Molecular Biology Reports, 2016)

Adaptive evolution of interleukin-3 (IL3), a gene associated with brain volume variation in general human populations - Ming Li; Liang Huang; Kaiqin Li; Yongxia Huo; Chunhui Chen; Jinkai Wang; Jiewei Liu; Zhenwu Luo; Chuansheng Chen; Qi Dong; Yong-gang Yao; Bing Su; et al. (Human Genetics, 2016)

Marine Carbon-Sulfur Biogeochemical Cycles during the Steptoean Positive Carbon Isotope Excursion (SPICE) in the Jiangnan Basin, South China - Yang Peng; Yongbo Peng; Xianguo Lang; Haoran Ma; Kangjun Huang; Fangbing Li; Bing Shen (Journal of Earth Science, 2016)

Chemotherapeutic agent CPT-11 eliminates peritoneal resident macrophages by inducing apoptosis - Mei-Yun Huang; Hao Pan; Yi-Dan Liang; Hong-Xia Wei; Li-Hui Xu; Qing-Bing Zha; Xian-Hui He; Dong-Yun Ouyang (Apoptosis, 2016)

Complete Genome of a Novel Pseudoalteromonas Phage PHq0 - Duo-bing Wang; Yan Li; Meng-qi Sun; Jin-peng Huang; Hong-bing Shao; Qi-lin Xin; Min Wang (Current Microbiology, 2016)

The prevalence of helminth parasites in Pelophylax nigromaculatus (Anura: Ranidae) from Shanghai, China - Qifei Men; Hongyu Han; Qiping Zhao; Weili Xia; Hui Dong; Shunhai Zhu; Ziwen Wang; Cong Li; Xuelong Zhu; Bing Huang (Acta Parasitologica, 2016)
Parasites are ubiquitous members of biotic communities. To investigate the infective status of helminth parasites in

Simultaneous detection of IgG and IgM antibodies against a recombinant polyprotein PstS1-LEP for tuberculosis diagnosis - Jun-Li Li; Xiang-Yu Huang; Hong-Bing Chen; Xin-Jing Wang; Chuan-Zhi Zhu; Ming Zhao; Qing-De Song; Hai-Yan Huang; Li Xiao; Xiu-Yun He (Infectious Diseases, 2015)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Effects of Fluoride on DNA Damage and Caspase-Mediated Apoptosis in the Liver of Rats - Guo Hua Song; Fu Bing Huang; Ji Ping Gao; Mao Lin Liu; Wen Biao Pang; Wei bin Li; Xiao Yan Yan; Mei Jun Huo; Xia Yang (Biological Trace Element Research, 2015)

P2X7 receptor of rat dorsal root ganglia is involved in the effect of moxibustion on visceral hyperalgesia - Shuangmei Liu; Qingming Shi; Qicheng Zhu; Ting Zou; Guilin Li; An Huang; Bing Wu; Lichao Peng; Miaomiao Song; Qin Wu; Qiuyu Xie; Weijian Lin; et al. (Purinergic Signalling, 2015)

A diagnostic method for aircraft turbulence based on high-resolution numerical weather prediction products - Xiao-kang Shi; Jian-wen Liu; Yao-dong Li; Bing Huang; Yong-qiang Tan (Natural Hazards, 2015)

Prevalence, quantification, and typing of human adenoviruses detected in river water in Taiwan - Zhon-Min Huang; Bing-Mu Hsu; Po-Min Kao; Tien-Yu Chang; Tsui-Kang Hsu; Ying-Ning Ho; Yi-Chun Yang; Yu-Li Huang (Environmental Science and Pollution Research, 2015)

Adsorption of a porcine reproductive and respiratory syndrome virus DNA vaccine candidate onto biodegradable nanoparticles improves immunogenicity in mice - Luping Du; Bin Li; Xiangwei Xu; Bing Sun; Fengjiao Pang; Libin Wen; Kehe Huang; Kongwang He (Archives of Virology, 2015)

Antibiotic resistance pattern and gene expression of non-typhoid Salmonella in riversheds - Chao-Yu Hsu; Bing-Mu Hsu; Wen-Tsai Ji; Jung-Sheng Chen; Tsui-Kang Hsu; Dar-Der Ji; Shao-Feng Tseng; Yi-Chou Chiu; Po-Min Kao; Yu-Li Huang (Environmental Science and Pollution Research, 2015)

The ctnG gene encodes carbonic anhydrase involved in mycotoxin citrinin biosynthesis from Monascus aurantiacus - Yan-Ping Li; Xiao Tang; Wei Wu; Yang Xu; Zhi-Bing Huang; Qing-Hua He (Food Additives & Contaminants: Part A, 2015)

Role of anti-inflammatory cytokines IL-4 and IL-13 in systemic sclerosis - Xiao-Lei Huang; Yu-Jie Wang; Jun-Wei Yan; Ya-Nan Wan; Bing Chen; Bao-Zhu Li; Guo-Jun Yang; Jing Wang (Inflammation Research, 2015)

Seasonal variation of Legionella in Taiwan’s reservoir and its relationships with environmental factors - Po-Min Kao; Bing-Mu Hsu; Tien-Yu Chang; Tsui-Kang Hsu; Kai-Jiun Tzeng; Yu-Li Huang (Environmental Science and Pollution Research, 2015)

Efficacy of Arsenic Trioxide in the Treatment of Malignant Pleural Effusion Caused by Pleural Metastasis of Lung Cancer - She-Ling Xie; Meng-Hang Yang; Kun Chen; Hai Huang; Xue-Wei Zhao; Yuan-Sheng Zang; Bing Li (Cell Biochemistry and Biophysics, 2015)

Comparative analysis of selected innate immune-related genes following infection of immortal DF-1 cells with highly pathogenic (H5N1) and low pathogenic (H9N2) avian influenza viruses - Ai-ling Liu; Yu-feng Li; Wenbao Qi; Xiu-li Ma; Ke-xiang Yu; Bing Huang; Ming Liao; Feng Li; Jie Pan; Min-xun Song (Virus Genes, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Seasonal distribution of potentially pathogenic Acanthamoeba species from drinking water reservoirs in Taiwan - Po-Min Kao; Bing-Mu Hsu; Tsui-Kang Hsu; Jorn-Hon Liu; Hsiang-Yu Chang; Wen-Tsai Ji; Kai-Jiun Tzeng; Shih-Wei Huang; Yu-Li Huang (Environmental Science and Pollution Research, 2015)

Retrospective Review on Obstetric Cases of Critically Ill and Dead Patients in Dongguan - Li-Han Shen; Yun-Yong Fang; Yan-Bing Zheng; Li-Juan Xiao; Su-Ran Huang; Xi-Zhen Liu; Li-Hua Cai (Cell Biochemistry and Biophysics, 2015)

First report of Hepatozoon (Apicomplexa: Adeleorina) from king ratsnakes (Elaphe carinata) in Shanghai, with description of a new species - Hongyu Han; Youling Wu; Hui Dong; Shunhai Zhu; Liujia Li; Qiping Zhao; Di Wu; Enle Pei; Yange Wang; Bing Huang (Acta Parasitologica, 2015)
Hepatozoon species are the most common hemoparasites of snakes. In this study, Hepatozoon parasites were examined for the first time in king rat snakes (Elaphe carinata) from Shanghai, China. All 10 snakes were found to be infected with Hepatozoon gamonts. The gamonts were folded back in a hook-wise fashion for about 3 μm at one end. Parasitemia levels ranged from 4-43 infected erythrocytes per 1,000 examined. The gamonts changed the morphology of the parasitized erythrocytes. Although the gamonts showed some distinct variations in both the parasite and its nucleus, phylogenetic analysis indicated that all the E. carinata in this study formed a monophyletic group, and were distinct from all other published Hepatozoon species. A new species, Hepatozoon chinensis, was proposed based on the molecular and morphologic evidence.

Radial oxygen loss has different effects on the accumulation of total mercury and methylmercury in rice - Xun Wang; Bing Li; Nora Fung-Yee Tam; Lu Huang; Xiaoli Qi; Hongbin Wang; Zhihong Ye; Mei Meng; Jianbo Shi (Plant and Soil, 2014)

Differences between the platform-margin shoal reservoirs and the platform-interior shoal reservoirs of the Middle Triassic Leikoupo Formation, Sichuan Basin, China - Xiong Ding; Xiucheng Tan; Ling Li; Liang Huang; Bing Luo; Qingsong Tang; Hualing Ma (Carbonates and Evaporites, 2014)

The expression profile and promoter analysis of β-N-acetylglucosaminidases in the silkworm Bombyx mori - Yuan-fen Zhai; Ming-xia Huang; Yu Wu; Guo-dong Zhao; Jie Du; Bing Li; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2014)

Geochemistry and genesis of authigenic pyrite from gas hydrate accumulation system in the Qilian Mountain permafrost, Qinghai, northwest China - PingKang Wang; YouHai Zhu; ZhenQuan Lu; Xia Huang; ShouJi Pang; Shuai Zhang; ShaoQing Jiang; QingHai Li; KaiLi Yang; Bing Li (Science China Earth Sciences, 2014)

Awareness is essential for differential delay eyeblink conditioning with soft-tone but not loud-tone conditioned stimuli - He Huang; Bing Wu; Qiong Li; Juan Yao; Xuan Li; Yi Yang; Guang-Yan Wu; Jian-Feng Sui (Neuroscience Bulletin, 2014)

Expression analysis and RNA interference of BmCarE-10 gene from Bombyx mori - Guo-dong Zhao; Ming-xia Huang; Yi-ling Zhang; Xue-cen Wang; Jie Du; Bing Li; Yu-hua Chen; Ya-xiang Xu; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2014)

Exploring the pattern of phenotypic and genetic polymorphism in the arsenic hyperaccumulator Pteris vittata L. (Chinese brake fern) - Bing Yang; Alessio Mengoni; Ye-Ling Huang; Xiong-Lei He; Jin-Tian Li; Bin Liao; Mi Zhou; Wen-Sheng Shu (Plant and Soil, 2013)

Overexpression of the AtSTK gene increases salt, PEG and ABA tolerance in Arabidopsis - Lei Bing; Cui-Cui Feng; Jing-Lan Li; Xiao-Xu Li; Bao-Cun Zhao; Yin-Zhu Shen; Zhan-Jing Huang; Rong-Chao Ge (Journal of Plant Biology, 2013)

A novel acridone akaloid from Atalantia buxifolia - Feng Shan; Yong-Qin Yin; Feng Huang; Yong-Chang Huang; Li-Bing Guo; Yu-Fei Wu (Natural Product Research, 2013)

A randomized, 12-week study of the effects of extended-release paliperidone (paliperidone ER) and olanzapine on metabolic profile, weight, insulin resistance, and β-cell function in schizophrenic patients - Shaohua Hu; Mingrong Yao; Bradley S. Peterson; Dongrong Xu; Jianbo Hu; Jianliang Tang; Bing Fan; Zhengluan Liao; Tianyi Yuan; Yaling Li; Weiqing Yue; Ning Wei; et al. (Psychopharmacology, 2013)

Elevated risk of opportunistic viral infection in patients with Crohn’s disease during biological therapies: a meta analysis of randomized controlled trials - Xiaobing Wang; Feng Zhou; Junzhang Zhao; Rui Zhou; Meifang Huang; Jin Li; Wei Wang; Shufang Xu; Bing Xia (European Journal of Clinical Pharmacology, 2013)

Identification and quantitative detection of Legionella spp. in various aquatic environments by real-time PCR assay - Po-Min Kao; Min-Che Tung; Bing-Mu Hsu; Yi-Chou Chiu; Cheng-Yu She; Shu-Min Shen; Yu-Li Huang; Wen-Chien Huang (Environmental Science and Pollution Research, 2013)

Population genetic structure, local adaptation, and conservation genetics of Kandelia obovata - Yu Ruan; Bing-Hong Huang; Shih-Jie Lai; Yu-Ting Wan; Jun-Qing Li; Shong Huang; Pei-Chun Liao (Tree Genetics & Genomes, 2013)

Antiarrhythmic effects and ionic mechanisms of allicin on myocardial injury of diabetic rats induced by streptozotocin - Wei Huang; Ye Wang; Yong-Gang Cao; Han-Ping Qi; Lei Li; Bing Bai; Yang Liu; Hong-Li Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Catalog of Erycina pusilla miRNA and categorization of reproductive phase-related miRNAs and their target gene families - Choun-Sea Lin; Jeremy J. W. Chen; Yao-Ting Huang; Chen-Tran Hsu; Hsiang-Chia Lu; Ming-Lun Chou; Li-Chi Chen; Chia-I Ou; Der-Chih Liao; Ysuan-Yu Yeh; Song-Bing Chang; Su-Chen Shen; et al. (Plant Molecular Biology, 2013)

Differential Legionella spp. survival between intracellular and extracellular forms in thermal spring environments - Po-Min Kao; Min-Che Tung; Bing-Mu Hsu; Shih-Yung Hsu; Jen-Te Huang; Jorn-Hon Liu; Yu-Li Huang (Environmental Science and Pollution Research, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Wnt/β-catenin signaling induces the aging of mesenchymal stem cells through promoting the ROS production - Da-yong Zhang; Yu Pan; Chong Zhang; Bing-xi Yan; Shan-shan Yu; Dong-ling Wu; Meng-meng Shi; Kai Shi; Xin-xiao Cai; Shuang-shuang Zhou; Jun-bo Wang; Jian-ping Pan; et al. (Molecular and Cellular Biochemistry, 2013)

Development and evaluation of a reverse transcription loop-mediated isothermal amplification assay for rapid detection of a new SFTS bunyavirus - Guoliang Yang; Bing Li; Lanzheng Liu; Weichu Huang; Wen Zhang; Yuandong Liu (Archives of Virology, 2012)

Discovery and profiling of novel and conserved microRNAs during flower development in Carya cathayensis via deep sequencing - Zheng Jia Wang; Jian Qin Huang; You Jun Huang; Zheng Li; Bing Song Zheng (Planta, 2012)

Association between TaqIB polymorphism of cholesteryl ester transfer protein and coronary artery disease in the Chinese population - Qi Yu; En-qi Liu; Si-hai Zhao; Ya-feng Li; Yan-li Wang; Yu-long Chen; Ke-na Wei; Bing-qiao Huang; Jian-lin Fan; Peng-hui Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Characterization of acute renal allograft rejection by proteomic analysis of renal tissue in rat - Gang Chen; Jing-bin Huang; Jie Mi; Yun-feng He; Xiao-hou Wu; Chun-li Luo; Si-min Liang; Jia-bing Li; Ya-xiong Tang; Jie Li (Molecular Biology Reports, 2012)

Insulin-like growth factor binding protein-6 interacts with the thyroid hormone receptor α1 and modulates the thyroid hormone-response in osteoblastic differentiation - Jia Qiu; Xiao-Li Ma; Xin Wang; Hong Chen; Bing-Ren Huang (Molecular and Cellular Biochemistry, 2012)

Effect of long-term administration of dietary β-1,3-glucan on growth, physiological, and immune responses in Litopenaeus vannamei (Boone, 1931) - Hong-Xia Zhao; Jun-Ming Cao; An-Li Wang; Zhen-Yu Du; Chao-Xia Ye; Yan-Hua Huang; Han-Bing Lan; Ting-Ting Zhou; Guo-Li Li (Aquaculture International, 2012)

Protective effects of IL-4 on Bacillus Calmette-Guerin and lipopolysaccharide induced immunological liver injury in mice - Nan N. Zhang; Nong Y. Huang; Xi K. Zhou; Xiao L. Luo; Chang Y. Liu; Yan Zhang; Ji Qiu; Yin B. Zhang; Xiu Teng; Can Luo; Xian C. Chen; Bing Kan; et al. (Inflammation Research, 2012)

Isolation and characterization of the citrinin biosynthetic gene cluster from Monascus aurantiacus - Yan-Ping Li; Yang Xu; Zhi-Bing Huang (Biotechnology Letters, 2012)

Characterization of mitochondrial genome of Formosan sambar (Rusa unicolor swinhoei) - Chia-Hsuan Chen; Hsiu-Lin Huang; Mu-Tzu Chang; Li-Chia Chiang; Shih-Lin Cheng; Bing-Tsan Liu; Chih-Hua Wang; Ming-Che Wu; Mu-Chiou Huang (Biologia, 2011)

The genetic profiling of preferentially expressed genes in murine splenic CD8α+ dendritic cells - Tao Li; Wu-Ying Li; Hui-Ling Bai; Hong-Bing Ma; Hu Zhang; Jiang-Mu Zhu; Xiao-Hong Li; Hong-Ying Huang; Yuan-Fang Ma; Xin-Ying Ji (Immunologic Research, 2011)

Development of genetically engineered CD4+ and CD8+ T cells expressing TCRs specific for a M. tuberculosis 38-kDa antigen - Wei Luo; Xiao-Bing Zhang; Yong-Ta Huang; Pei-Pei Hao; Zhen-Min Jiang; Qian Wen; Ming-Qian Zhou; Qi Jin; Li Ma (Journal of Molecular Medicine, 2011)

Production, purification and characterization of a thermostable laccase from a tropical white-rot fungus - Li-Qiong Guo; Shuo-Xin Lin; Xiao-Bing Zheng; Zi-Rou Huang; Jun-Fang Lin (World Journal of Microbiology and Biotechnology, 2011)

A Sandwiched Biological Fluorescent Probe for the Diagnosis of Human Ovarian Tumor Based on TiO2 Nanoparticles - Peisi Zhu; Shasheng Huang; Mengyao Li; Na Ding; Bing Peng; Lingmi Kong; Yang Bo (Journal of Fluorescence, 2011)

Inhibition of phosphodiesterase-4 reverses memory deficits produced by Aβ25–35 or Aβ1–40 peptide in rats - Yu-Fang Cheng; Chuang Wang; Huan-Bing Lin; Yun-Feng Li; Ying Huang; Jiang-Ping Xu; Han-Ting Zhang (Psychopharmacology, 2010)

Damage consequence chain mapping after the Wenchuan Earthquake using remotely sensed data - Huadong Guo; Jianwen Ma; Bing Zhang; Zhen Li; Jun Huang; Lanwei Zhu (International Journal of Remote Sensing, 2010)

Notch signaling maintains proliferation and survival of the HL60 human promyelocytic leukemia cell line and promotes the phosphorylation of the Rb protein - Guo-Hui Li; Yu-Zhen Fan; Xiao-Wei Liu; Bing-Fang Zhang; Dan-Dan Yin; Fei He; Si-Yong Huang; Zhi-Jie Kang; Heng Xu; Qiang Liu; Yan-Lan Wu; Xiao-Li Niu; et al. (Molecular and Cellular Biochemistry, 2010)

Erratum to: RegIV expression showing specificity to gastrointestinal tract and its potential role in diagnosing digestive tract neuroendocrine tumor - Feng-ying Li; Xiao-bin Ren; En-ping Xu; Qiong Huang; Hong-qiang Sheng; Bing-jian Lv; Mao-de Lai (Journal of Zhejiang University-SCIENCE B, 2010)

RegIV expression showing specificity to gastrointestinal tract and its potential role in diagnosing digestive tract neuroendocrine tumor - Feng-ying Li; Xiao-bin Ren; En-ping Xu; Qiong Huang; Hong-qiang Sheng; Bing-jian Lv; Mao-de Lai (Journal of Zhejiang University-SCIENCE B, 2010)

Association of TNFAIP3 polymorphism with rheumatic heart disease in Chinese Han population - Rong Hua; Ji-bin Xu; Jiu-cun Wang; Li Zhu; bing Li; Yang Liu; Sheng-dong Huang; Li Jin; Zhi-yun Xu; Xiao-feng Wang (Immunogenetics, 2009)

Oct-1 functions as a transactivator in the hormonal induction of β-casein gene expression - Bing Dong; Chengfei Huang; Defa Li; Feng-Qi Zhao (Molecular and Cellular Biochemistry, 2009)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

Association of the mutation for the human carboxypeptidase E gene exon 4 with the severity of coronary artery atherosclerosis - En-Zhi Jia; Jie Wang; Zhi-Jian Yang; Tie-Bing Zhu; Lian-Sheng Wang; Hui Wang; Chun-Jian Li; BO Chen; Ke-Jiang Cao; Jun Huang; Wen-Zhu Ma (Molecular Biology Reports, 2009)

Intensive water quality monitoring in a Taiwan bathing beach - Bing-Mu Hsu; Yu-Li Huang (Environmental Monitoring and Assessment, 2008)

Human tau protein forms complex with PrP and some GSS- and fCJD-related PrP mutants possess stronger binding activities with tau in vitro - Xiao-Fan Wang; Chen-Fang Dong; Jin Zhang; Yan-Zhen Wan; Feng Li; Yin-Xia Huang; Lu Han; Bing Shan; Chen Gao; Jun Han; Xiao-Ping Dong (Molecular and Cellular Biochemistry, 2008)

Remediation of pentachlorophenol-contaminated soil by composting with immobilized Phanerochaete chrysosporium - Xiao-yun Jiang; Guang-ming Zeng; Dan-lian Huang; Yang Chen; Fang Liu; Guo-he Huang; Jian-bing Li; Bei-dou Xi; Hong-liang Liu (World Journal of Microbiology and Biotechnology, 2006)

Laccase activities of a soil fungus Penicillium simplicissimum in relation to lignin degradation - Guang Ming Zeng; Hong Yan Yu; Hong Li Huang; Dan Lian Huang; Yao Ning Chen; Guo He Huang; Jian Bing Li (World Journal of Microbiology and Biotechnology, 2006)

Functional analysis of helicase and three tandem HRDC domains of RecQ in Deinococcus radiodurans - Li-fen Huang; Xiao-ting Hua; Hui-ming LU; Guan-jun Gao; Bing Tian; Bing-hui Shen; Yue-jin Hua (Journal of Zhejiang University-SCIENCE B, 2006)

Quantitative trait loci mapping and epistatic analysis for grain yield and yield components using molecular markers with an elite maize hybrid - Jian-bing Yan; Hua Tang; Yi-qin Huang; Yong-lian Zheng; Jian-sheng Li (Euphytica, 2006)

GIS-based distributed model for simulating runoff and sediment load in the Malian River Basin - Y. F. Huang; X. Chen; G. H. Huang; Bing Chen; G. M. Zeng; J. B. Li; J. Xia (Hydrobiologia, 2003)

Circular F-actin bundles and a G-actin gradient in pollen and pollen tubes of Lilium davidii - Yan Li; Sze-Yong Zee; Yi-Min Liu; Bing-Quan Huang; Lung-Fei Yen (Planta, 2001)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)